Laminates, packaging materials

The laminate structure with a stretched polyolefin film, heat-sealing layer, and polysiloxane-coated layer addresses the challenge of recyclability and heat resistance in packaging materials, ensuring efficient recycling and maintaining productivity through improved adhesion and crosslinking.

JP7605369B2Active Publication Date: 2024-12-24DIC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024506112
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-03-10
Filing Date
2023-03-02
Publication Date
2024-12-24
Estimated Expiration
2043-03-02

AI Technical Summary

Technical Problem

Existing packaging laminates face challenges in achieving both recyclability and heat resistance, as laminates with stretched polyolefin films require lower heat sealing temperatures, reducing productivity, while those with polyester or nylon films are difficult to recycle due to incompatible resin types.

Method used

A laminate structure comprising a stretched polyolefin film, a heat-sealing layer, and a coat layer with a polysiloxane and vinyl polymer segment, enhancing recyclability and heat resistance by improving adhesion and crosslinking density.

Benefits of technology

The laminate achieves excellent recyclability and heat resistance, allowing for efficient recycling and maintaining productivity by using a polysiloxane segment to improve heat sealing properties without compromising mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605369000001
    Figure 0007605369000001
  • Figure 0007605369000002
    Figure 0007605369000002
  • Figure 0007605369000003
    Figure 0007605369000003
Patent Text Reader

Abstract

Provided are: a laminate having excellent recyclability and having, when a stretched polyolefin film is used for the layer on the outer layer side as seen from the content after the laminate is formed into a bag, more excellent heat resistance than conventional laminates; and a packaging material using the laminate. The laminate contains a composite resin (A) comprising a heat seal layer, a stretched polyolefin film, and a coat layer in this order, the coat layer having a polysiloxane segment (a1) and a vinyl-based polymer segment (a2). The packaging material is obtained by forming the laminate into a bag.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate which has excellent recyclability and heat resistance and is suitable for food packaging, and to a packaging material obtained by using the laminate. [Background technology]

[0002] Packaging materials used for packaging food and daily necessities are usually made of a laminate in which a heat-sealable film such as an unstretched polyethylene film or polypropylene film is bonded to a resin film with excellent heat resistance and strength such as a polyester film or a nylon film using an adhesive (Patent Documents 1 and 2). Meanwhile, in recent years, with the growing demand for the creation of a recycling-oriented society, attempts have been made to recycle and reuse packaging materials. However, in laminates in which different types of resin films are bonded together as described above, it is difficult to separate the resins by type, and they are not suitable for recycling. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-004799 A [Patent Document 2] JP 2004-238050 A Summary of the Invention [Problem to be solved by the invention]

[0004] A laminate for packaging materials with excellent recyclability may be one that uses a stretched polyolefin film such as stretched polypropylene or stretched polyethylene film on the outer layer side from the content side, and an unstretched polypropylene film or low-density polyethylene film on the inner layer side (sealant film). Since olefin resin accounts for most of the entire laminate, such a laminate has excellent recyclability compared to laminates using different types of base materials.

[0005] However, since olefin-based films have lower heat resistance than polyester and nylon films, laminates using stretched polyolefin films on the outer layer side will shrink when bags are made at the same heat sealing temperature as when polyester and nylon films are used. To avoid this, it is necessary to heat seal for a longer time to make bags at a lower temperature than before, which reduces productivity.

[0006] The present invention has been made in view of the above background, and an object of the present invention is to provide a laminate having excellent recyclability and heat resistance, and a packaging material using said laminate. [Means for solving the problem]

[0007] The present invention relates to a laminate comprising, in this order, a heat seal layer, a stretched polyolefin film, and a coating layer, the coating layer containing a composite resin (A) having a polysiloxane segment (a1) and a vinyl polymer segment (a2). Effect of the Invention

[0008] According to the laminate of the present invention, it is possible to provide a laminate and a packaging material having excellent heat resistance and recyclability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Laminate> The laminate of the present invention has a heat seal layer, a stretched polyolefin film, and a coating layer in this order.

[0010] (oriented polyolefin film) Examples of the oriented polyolefin film include a high density polyethylene film (HDPE), a uniaxially oriented polyethylene film (MDOPE), a biaxially oriented polyethylene film (OPE), and a biaxially oriented polypropylene film (OPP).

[0011] The thickness of the stretched polyolefin film can be appropriately adjusted depending on the purpose, but is preferably from 5 μm to 300 μm in terms of the balance between mechanical strength and processability, and more preferably from 7 μm to 100 μm.

[0012] The stretched polyolefin film may be subjected to a surface treatment, which can improve the adhesion between adjacent layers. The method of the surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, and chemical treatments such as oxidation treatment using chemicals.

[0013] (Heat seal layer) The heat seal layer is made of an olefin resin and has a heat sealability that melts and fuses with each other by heat. Specific examples include films made of olefin resins such as polyethylene, such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear (linear) low-density polyethylene, polypropylene, ethylene-propylene copolymer, and polymethylpentene. The heat seal layer may be surface-treated by the same method as the stretched polyolefin film.

[0014] The thickness of the heat seal layer is preferably 15 μm or more and 500 μm or less, more preferably 20 μm or more and 250 μm or less, and even more preferably 30 μm or more and 100 μm or less, which can improve the processability and puncture resistance of the laminate of the present invention while maintaining the heat sealability of the heat sealable resin layer.

[0015] (Coat layer) The coating layer is provided directly on the stretched polyolefin film or via a printing layer described later. When the laminate of the present invention is made into a bag, the coating layer is located at the outermost layer from the content side and is the layer that comes into contact with the heat seal bar during bag making. The coating layer is a cured coating film of a coating agent containing a composite resin (A) having a polysiloxane segment (a1) and a vinyl polymer segment (a2). By disposing such a layer as the outermost layer of the laminate, the heat resistance of the laminate can be improved. The coating layer may be provided on the entire surface of the stretched polyolefin film, or may be provided partially only on the part that comes into contact with the heat seal bar during bag making of the laminate of the present invention and its periphery.

[0016] The polysiloxane segment (a1) is a segment obtained by condensing a silane compound having a silanol group and / or a hydrolyzable silyl group, and has a structural unit represented by the following general formula (1) and / or general formula (2) and a silanol group and / or a hydrolyzable silyl group. If the content of the polysiloxane segment (a1) is 10 to 90% by weight based on the total solid content of the composite resin (A), it is preferable because it facilitates bonding with the inorganic particles (m) described below.

[0017] [ka]

[0018] [ka]

[0019] R in the above general formulas (1) and (2) 1 , R 2 and R 3 are each independently -R 4 -CH=CH2, -R 4 -C(CH3)=CH2, -R 4 -O-CO-C(CH3)=CH2 and -R 4-O-CO-CH=CH2, or a group having a polymerizable double bond selected from the group consisting of groups represented by the following formula (3) (wherein R 4 represents a single bond or an alkylene group having 1 to 6 carbon atoms), an alkyl group having 1 to 6 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an aryl group, an aralkyl group having 7 to 12 carbon atoms, or an epoxy group.

[0020] [ka] (In the general formula (3), n is an integer of 1 to 5, and the structure Q represents either -CH=CH2 or -C(CH3)=CH2.)

[0021] The structural units represented by the above general formula (1) and / or (2) are three-dimensional network polysiloxane structural units in which two or three of the silicon bonds are involved in crosslinking. Although they form a three-dimensional network structure, they do not form a dense network structure, so they do not gel and have good storage stability.

[0022] In the above general formulas (1) and (2), R 4 Examples of the alkylene group having 1 to 6 carbon atoms in the formula (I) include a methylene group, an ethylene group, a propylene group, an isopropylene group, a butylene group, an isobutylene group, a sec-butylene group, a tert-butylene group, a pentylene group, an isopentylene group, a neopentylene group, a tert-pentylene group, a 1-methylbutylene group, a 2-methylbutylene group, a 1,2-dimethylpropylene group, a 1-ethylpropylene group, a hexylene group, an isohexylene group, a 1-methylpentylene group, a 2-methylpentylene group, a 3-methylpentylene group, a 1,1-dimethylbutylene group, a 1,2-dimethylbutylene group, a 2,2-dimethylbutylene group, a 1-ethylbutylene group, a 1,1,2-trimethylpropylene group, a 1,2,2-trimethylpropylene group, a 1-ethyl-2-methylpropylene group, and a 1-ethyl-1-methylpropylene group. From the viewpoint of easy availability of raw materials, a single bond or an alkylene group having 2 to 4 carbon atoms is preferred.

[0023] Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, and a 1-ethyl-1-methylpropyl group.

[0024] Examples of the cycloalkyl group having 3 to 8 carbon atoms include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.

[0025] Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group. Examples of the aralkyl group having 7 to 12 carbon atoms include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.

[0026] Also, R 1 , R 2 and R 3 When at least one of the groups has a polymerizable double bond, the resin can be cured by active energy rays or the like. Due to the two curing mechanisms of active energy rays and a condensation reaction of a silanol group and / or a hydrolyzable silyl group, the crosslink density of the resulting cured product is increased, which is preferable since a cured product having better abrasion resistance and low linear expansion can be formed.

[0027] The polysiloxane segment (a1) preferably has two or more groups having a polymerizable double bond, more preferably has 3 to 200 groups, and even more preferably has 3 to 50 groups. This allows a molded product with lower linear expansion to be obtained. Specifically, if the content of the polymerizable double bond in the polysiloxane segment (a1) is 3 to 35% by weight, the linear expansion coefficient can be designed to be lower than that of a stretched polyolefin film, and the heat resistance of the laminate can be improved. Here, the polymerizable double bond is a general term for a group that can undergo a propagation reaction by a free radical, among a vinyl group, a vinylidene group, or a vinylene group. The content of the polymerizable double bond indicates the weight % of the vinyl group, the vinylidene group, or the vinylene group in the polysiloxane segment.

[0028] As the group having a polymerizable double bond, any known functional group containing a vinyl group, a vinylidene group, or a vinylene group can be used. Among them, -R 4 -C(CH3)=CH2 or -R 4 The (meth)acryloyl group represented by -O-CO-C(CH3)=CH2 is preferred because it has high reactivity when cured with active energy rays and has good compatibility with the vinyl polymer segment (a2) described below.

[0029] In addition, when the group having a polymerizable double bond is a group represented by the above general formula (3), the structure Q in the formula indicates that a plurality of vinyl groups may be bonded to the aromatic ring. For example, when two Qs are bonded to the aromatic ring, the following structure (4) may also be included.

[0030] [ka]

[0031] Since structures such as the styryl group do not contain oxygen atoms, they are less susceptible to oxidative decomposition originating from oxygen atoms and have high thermal decomposition resistance, making them suitable for applications requiring heat resistance. This is thought to be because the bulky structure inhibits oxidation reactions. In addition, the -R 4 -CH=CH2, -R 4 It is preferable that the compound has a group having a polymerizable double bond selected from the group consisting of -C(CH3)=CH2.

[0032] In the polysiloxane segment (a1), R 1 , R 2 and R 3 When at least one of the groups is an epoxy group, the resin can be cured by heat curing or active energy ray curing. Due to the two curing mechanisms of the condensation reaction of the epoxy group and the silanol group and / or the hydrolyzable silyl group, the crosslink density of the resulting cured product is increased, and a cured product having an excellent low linear expansion coefficient can be formed.

[0033] In this specification, the silanol group refers to a silicon-containing group having a hydroxyl group directly bonded to a silicon atom. Specifically, the silanol group is preferably a silanol group formed by bonding an oxygen atom having a bond to a hydrogen atom in a structural unit represented by general formula (1) and / or (2).

[0034] In this specification, the hydrolyzable silyl group refers to a silicon-containing group having a hydrolyzable group directly bonded to a silicon atom, and examples thereof include groups represented by the following general formula (5).

[0035] [ka] (In formula (6), R 5 R represents a monovalent organic group such as an alkyl group, an aryl group, or an aralkyl group. 6is a hydrolyzable group selected from the group consisting of a halogen atom, an alkoxy group, an acyloxy group, a phenoxy group, an aryloxy group, a mercapto group, an amino group, an amido group, an aminooxy group, an iminoxy group, and an alkenyloxy group, and b is an integer of 0 to 2.

[0036] R 5 Examples of the alkyl group in the formula (I) include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, an isopentyl group, a neopentyl group, a tert-pentyl group, a 1-methylbutyl group, a 2-methylbutyl group, a 1,2-dimethylpropyl group, a 1-ethylpropyl group, a hexyl group, an isohexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 1,1-dimethylbutyl group, a 1,2-dimethylbutyl group, a 2,2-dimethylbutyl group, a 1-ethylbutyl group, a 1,1,2-trimethylpropyl group, a 1,2,2-trimethylpropyl group, a 1-ethyl-2-methylpropyl group, and a 1-ethyl-1-methylpropyl group. Examples of the aryl group include a phenyl group, a naphthyl group, a 2-methylphenyl group, a 3-methylphenyl group, a 4-methylphenyl group, a 4-vinylphenyl group, and a 3-isopropylphenyl group. Examples of the aralkyl group include a benzyl group, a diphenylmethyl group, and a naphthylmethyl group.

[0037] R 6 In the above, examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, an isopropoxy group, a butoxy group, a sec-butoxy group, and a tert-butoxy group. Examples of the acyloxy group include formyloxy, acetoxy, propanoyloxy, butanoyloxy, pivaloyloxy, pentanoyloxy, phenylacetoxy, acetoacetoxy, benzoyloxy, and naphthoyloxy. Aryloxy groups include, for example, phenyloxy, naphthyloxy, and the like. Examples of the alkenyloxy group include a vinyloxy group, an allyloxy group, a 1-propenyloxy group, an isopropenyloxy group, a 2-butenyloxy group, a 3-butenyloxy group, a 2-pentenyloxy group, a 3-methyl-3-butenyloxy group, and a 2-hexenyloxy group.

[0038] R 6 The hydrolyzable group represented by the general formula (5) becomes a silanol group by hydrolysis of the hydrolyzable group represented by the general formula (5). Among these, a methoxy group and an ethoxy group are preferred because of their excellent hydrolyzability. Specifically, the hydrolyzable silyl group is preferably a hydrolyzable silyl group in which an oxygen atom having a bond in a structural unit represented by general formula (1) and / or general formula (2) is bonded to or substituted with the hydrolyzable group.

[0039] Silanol groups and hydrolyzable silyl groups undergo a hydrolysis and condensation reaction between the hydroxyl groups in the silanol groups and the hydrolyzable groups in the hydrolyzable silyl groups, thereby increasing the crosslinking density of the polysiloxane structure and forming a cured product that has excellent abrasion resistance and low linear expansion. It is also used when bonding a polysiloxane segment (a1) containing a silanol group or a hydrolyzable silyl group to a vinyl polymer segment (a2) described below via a bond represented by the following general formula (6).

[0040] [ka]

[0041] The polysiloxane segment (a1) is not particularly limited except that it has the structural units represented by the general formula (1) and / or (2) and a silanol group and / or a hydrolyzable silyl group, and may contain other groups. For example, R 1 is a structural unit having a polymerizable double bond, and R in general formula (1)1 In the general formula (1), R 1 is a structural unit having a polymerizable double bond, and R in general formula (1) 1 is an alkyl group such as a methyl group, and R in the general formula (2) 2 and R 3 In the general formula (1), R 1 is a structural unit having a polymerizable double bond, and R in general formula (2) 2 and R 3 The polysiloxane segment (a1) may also be a polysiloxane segment in which a structural unit in which the alkyl group such as a methyl group coexists with the structural unit in which the alkyl group is a methyl group or the like.

[0042] The vinyl polymer segment (a2) is a polymer segment obtained by polymerizing a vinyl group or (meth)acrylic group-containing monomer, and examples thereof include a vinyl polymer segment, an acrylic polymer segment, a vinyl / acrylic copolymer segment, etc., which are preferably selected appropriately depending on the application. The composite resin (A) used in the present invention has the vinyl polymer segment (a2), and therefore has excellent adhesion to a stretched polyolefin film.

[0043] The acrylic polymer segment can be obtained, for example, by polymerizing or copolymerizing a general-purpose (meth)acrylic monomer. The (meth)acrylic monomer is not particularly limited, and examples thereof include alkyl (meth)acrylates having an alkyl group having 1 to 22 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate; aralkyl (meth)acrylates, such as benzyl (meth)acrylate and 2-phenylethyl (meth)acrylate; cyclohexyl (meth)acrylate; and the like. cycloalkyl (meth)acrylates such as acrylate and isobornyl (meth)acrylate; ω-alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate and 4-methoxybutyl (meth)acrylate; vinyl carboxylate esters such as vinyl acetate, vinyl propionate, vinyl pivalate, and vinyl benzoate; alkyl esters of crotonic acid such as methyl crotonate and ethyl crotonate; and dialkyl esters of unsaturated dibasic acids such as dimethyl maleate, di-n-butyl maleate, dimethyl fumarate, and dimethyl itaconate.

[0044] Specific examples of the vinyl polymer segment include aromatic vinyl polymer segments, polyolefin polymers, and fluoroolefin polymers, and copolymers thereof may also be used. To obtain these vinyl polymers, vinyl group-containing monomers may be polymerized, and specifically, α-olefins such as ethylene, propylene, 1,3-butadiene, and cyclopentylethylene; vinyl compounds having aromatic rings such as styrene, 1-ethynyl-4-methylbenzene, divinylbenzene, 1-ethynyl-4-methylethylbenzene, benzonitrile, acrylonitrile, p-tert-butylstyrene, 4-vinylbiphenyl, 4-ethynylbenzyl alcohol, 2-ethynylnaphthalene, and phenanthrene-9-ethynyl; fluoroolefins such as vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, and chlorotrifluoroethylene may be suitably used. More preferred are vinyl compounds having aromatic rings, such as styrene and p-tert-butylstyrene.

[0045] The vinyl / acrylic copolymer segment may be one obtained by copolymerizing these (meth)acrylic monomers with a vinyl group-containing monomer.

[0046] The polymerization method, solvent, or polymerization initiator used for copolymerizing the monomers is not particularly limited, and the vinyl polymer segment (a2) can be obtained by a known method. For example, the vinyl polymer segment (a2) can be obtained by various polymerization methods such as bulk radical polymerization, solution radical polymerization, and non-aqueous dispersion radical polymerization using a polymerization initiator such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), tert-butyl peroxypivalate, tert-butyl peroxybenzoate, tert-butyl peroxy-2-ethylhexanoate, di-tert-butyl peroxide, cumene hydroperoxide, or diisopropyl peroxycarbonate.

[0047] The number average molecular weight of the vinyl polymer segment (a2) is preferably in the range of 500 to 200,000 in terms of number average molecular weight (hereinafter abbreviated as Mn), which can prevent thickening and gelation during production of the composite resin (A) and provides excellent durability. Among these, Mn is more preferably in the range of 700 to 100,000, and even more preferably in the range of 1,000 to 50,000.

[0048] In this specification, the number average molecular weight of the vinyl polymer segment (a2) is a value measured by gel permeation chromatography (GPC) under the following conditions. Measurement equipment: Gel permeation chromatograph GCP-244 (WATERS) Column: Shodex HFIP 80M x 2 (Showa Denko Co., Ltd.) Solvent: Dimethylformamide Flow rate: 0.5ml / min Temperature: 23℃ Sample concentration: 0.1% Solubility: Completely dissolved Filtration: Myshoridisk W-13-5 Injection volume: 0.300ml Detector: R-401 type differential refractive index detector (WATERS) Molecular weight calibration: Polystyrene (standard)

[0049] The vinyl polymer segment (a2) has a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom in the vinyl polymer segment (a2) in order to form a composite resin (A) bonded to the polysiloxane segment (a1) by a bond represented by the general formula (6). These silanol groups and / or hydrolyzable silyl groups become bonds represented by the general formula (6) in the composite resin (A), so they are hardly present in the vinyl polymer segment (a2) in the composite resin (A) which is the final product. However, there is no problem even if the silanol group and / or the hydrolyzable silyl group remain in the vinyl polymer segment (a2), and when the composite resin (A) is cured, a hydrolysis condensation reaction proceeds between the hydroxyl group in the silanol group and the hydrolyzable group in the hydrolyzable silyl group, so that the crosslink density of the polysiloxane structure of the obtained cured product is increased, and a cured product having excellent heat resistance and abrasion resistance can be formed.

[0050] To introduce a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom into the vinyl polymer segment (a2), specifically, a vinyl monomer containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond may be used in combination with a vinyl group-polymerizing monomer and a (meth)acrylic monomer when polymerizing the vinyl polymer segment (a2).

[0051] Examples of vinyl monomers containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom include vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltrichlorosilane, 2-trimethoxysilylethyl vinyl ether, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltrichlorosilane, etc. Among them, vinyltrimethoxysilane and 3-(meth)acryloyloxypropyltrimethoxysilane are preferred because they can easily proceed with the hydrolysis reaction and can easily remove by-products after the reaction.

[0052] The vinyl polymer segment (a2) may have various functional groups. For example, a group having a polymerizable double bond, an epoxy group, an alcoholic hydroxyl group, an acidic group, etc., and the functional group can be introduced by blending a vinyl monomer having the corresponding functional group during polymerization. If the vinyl polymer segment (a2) has an acid group, it is preferable because the coating layer is more easily peeled off from the stretched polyolefin film when subjected to an alkali treatment described later.

[0053] Examples of vinyl monomers having an epoxy group include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, vinylcyclohexene oxide, glycidyl vinyl ether, methyl glycidyl vinyl ether, and allyl glycidyl ether.

[0054] Examples of vinyl monomers having an alcoholic hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, di-2-hydroxyethyl fumarate, mono-2-hydroxyethyl monobutyl fumarate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, and "PLACCEL FM or PLACCEL FA" (caprolactone addition monomer manufactured by Daicel Chemical Industries, Ltd.), as well as various hydroxyalkyl esters of α,β-ethylenically unsaturated carboxylic acids, or adducts of these with ε-caprolactone.

[0055] Monomers containing acidic groups include acrylic acid, methacrylic acid, maleic acid, itaconic acid, citraconic acid, mesaconic acid, maleic anhydride, 4-methylcyclohex-4-ene-1,2-dicarboxylic anhydride, bicyclo[2.2.2]oct-5-ene-2,3-dicarboxylic anhydride, 1,2,3,4,5,8,9,10-octahydronaphthalene-2,3-dicarboxylic anhydride, 2-octa-1,3-diketospiro[4. 4] non-7-ene, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, maleopimaric acid, tetrahydrophthalic anhydride, methyl-bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, methyl-norbornene-5-ene-2,3-dicarboxylic anhydride, norborn-5-ene-2,3-dicarboxylic anhydride, sulfonated styrene, vinylbenzenesulfonamide, and the like.

[0056] The coating agent used to form the coat layer may contain inorganic particles (m) in addition to the composite resin (A). Furthermore, the composite resin (A) and the inorganic particles (m) may be bonded together. The composite resin (A) and the inorganic particles (m) can be bonded together via a siloxane bond in the polysiloxa segment (a1) contained in the composite resin (A). The presence of the inorganic particles (m) in the coat layer can further improve the heat resistance of the coat layer. In addition, the bond between the composite resin (A) and the inorganic particles (m) can be expected to have the effect of making the coat layer more easily peeled off from the stretched polyolefin film when subjected to an alkali treatment described later.

[0057] The inorganic particles (m) are not particularly limited as long as they do not impair the effects of the present invention, but when they are bonded to the polysiloxane segment (a1) via a siloxane bond, they are selected from those having a functional group capable of forming a siloxane bond. The functional group capable of forming a siloxane bond may be any functional group capable of forming a siloxane bond, such as a hydroxyl group, a silanol group, or an alkoxysilyl group. The functional group capable of forming a siloxane bond may be possessed by the inorganic particles (m) themselves, or the functional group may be introduced by modifying the inorganic particles (m). The method for modifying the inorganic particles (m) may be a known and commonly used method, such as a method of treating with a silane coupling agent or coating with a resin having a functional group capable of forming a siloxane bond.

[0058] As the inorganic particles (m), for example, alumina, magnesia, titania, zirconia, silica (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, ultrafine amorphous silica, etc.), etc. are preferable because they have excellent heat resistance. Alternatively, boron nitride, aluminum nitride, alumina oxide, titanium oxide, magnesium oxide, zinc oxide, silicon oxide, etc. are preferable because they have excellent thermal conductivity. The inorganic particles (m) may be used alone or in combination of multiple types.

[0059] For example, when silica is used as the inorganic particles (m), known silica particles such as powdered silica and colloidal silica can be used without any particular limitation. Commercially available powdered silica particles include, for example, Aerosil 50 and 200 manufactured by Nippon Aerosil Co., Ltd., Sildex H31, H32, H51, H52, H121, and H122 manufactured by Asahi Glass Co., Ltd., E220A and E220 manufactured by Nippon Silica Industry Co., Ltd., SYLYSIA470 manufactured by Fuji Silysia Co., Ltd., and SG flake manufactured by Nippon Sheet Glass Co., Ltd. Commercially available colloidal silica includes, for example, methanol silica sol, IPA-ST, PGM-ST, NBA-ST, XBA-ST, DMAC-ST, ST-UP, ST-OUP, ST-20, ST-40, ST-C, ST-N, ST-O, ST-50, and ST-OL manufactured by Nissan Chemical Industries, Ltd.

[0060] Surface-modified silica particles may also be used, for example, the silica particles exemplified above are surface-treated with a reactive silane coupling agent having a hydrophobic group, or modified with a compound having a (meth)acryloyl group.Commercially available powdered silica modified with a compound having a (meth)acryloyl group includes Aerosil RM50, R7200, R711, etc. manufactured by Nippon Aerosil Co., Ltd., commercial colloidal silica modified with a compound having a (meth)acryloyl group includes MIBK-SD, MEK-SD, etc. manufactured by Nissan Chemical Industries, Ltd., and colloidal silica surface-treated with a reactive silane coupling agent having a hydrophobic group includes MIBK-ST, MEK-ST, etc. manufactured by Nissan Chemical Industries, Ltd.

[0061] The shape of the silica particles is not particularly limited, and spherical, hollow, porous, rod-like, plate-like, fibrous, or amorphous silica particles can be used. For example, commercially available hollow silica particles include Silinax manufactured by Nittetsu Mining Co., Ltd.

[0062] As the titanium oxide particles, not only extender pigments but also ultraviolet light responsive photocatalysts can be used, for example, anatase type titanium oxide, rutile type titanium oxide, brookite type titanium oxide, etc. can be used. Furthermore, particles designed to respond to visible light by doping different elements into the crystal structure of titanium oxide can also be used. As the element to be doped into titanium oxide, anionic elements such as nitrogen, sulfur, carbon, fluorine, phosphorus, etc., and cationic elements such as chromium, iron, cobalt, manganese, etc. are preferably used. In addition, as the form, powder, sol dispersed in an organic solvent or water, or slurry can be used. As commercially available powdered titanium oxide particles, for example, Aerosil P-25 manufactured by Nippon Aerosil Co., Ltd., ATM-100 manufactured by Teika Co., Ltd., etc. can be used. In addition, as commercially available slurry-like titanium oxide particles, for example, TKD-701 manufactured by Teika Co., Ltd., etc. can be used.

[0063] The primary particle diameter of the inorganic particles (m) is preferably in the range of 5 to 200 nm. If it is 5 nm or more, the inorganic particles (m) in the dispersion are well dispersed, and if the diameter is within 200 nm, the strength of the cured product is good. More preferably, it is 10 nm to 100 nm. The "particle diameter" here is measured using a scanning electron microscope (TEM) or the like.

[0064] From the viewpoint of the balance between adhesion to the stretched polyolefin film and heat resistance, the inorganic particles (m) can be blended in a ratio of 5 to 90% by weight based on the total solid content of the composite resin (A) and the inorganic particles (m), and the blending amount may be changed as appropriate depending on the purpose. From the viewpoint of heat resistance, the blending amount of the inorganic particles (m) based on the total solid content of the composite resin (A) and the inorganic particles (m) is preferably 20% by mass or more.

[0065] When the composite resin (A) and the inorganic particles (m) are bonded to each other, the composite resin (A) can be obtained by a production method characterized by having a step 1 of synthesizing a vinyl polymer segment (a2) having a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom, a step 2 of mixing an alkoxysilane with the inorganic particles (m), and a step 3 of condensing the alkoxysilane. At this time, each step may be carried out separately or simultaneously. For example, the composite resin (A) can be produced by the following method.

[0066] <Method 1> A method in which the vinyl polymer segment (a2) having a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom obtained in step 1, a silane compound containing a silanol group and / or a hydrolyzable silyl group, and inorganic particles (m) are simultaneously mixed in step 2, and this mixture is subjected to condensation of the silane compound containing a silanol group and / or a hydrolyzable silyl group in step 3 to form a polysiloxane segment (a1) and form bonds between the vinyl polymer segment (a2) and the inorganic particles (m).

[0067] <Method 2> A method in which a silane compound containing a silanol group and / or a hydrolyzable silyl group is mixed with inorganic particles (m) in step 2, the silane compound containing a silanol group and / or a hydrolyzable silyl group is condensed in step 3 to form polysiloxane segments (a1) and inorganic particle bonds, and then the vinyl polymer segments (a2) having silanol groups and / or hydrolyzable silyl groups obtained in step 1 are hydrolyzed and condensed again with the polysiloxane segments (a1) and inorganic particles (m) in step 3 to form bonds.

[0068] Step 1 is a step of synthesizing a vinyl polymer segment (a2) having a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom. To introduce a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon atom into the vinyl polymer segment (a2), specifically, a vinyl monomer containing a silanol group and / or a hydrolyzable silyl group directly bonded to a carbon bond may be used in combination with a vinyl group-polymerizing monomer and a (meth)acrylic monomer when polymerizing the vinyl polymer segment (a2).

[0069] Furthermore, after that, a silane compound containing a silanol group and / or a hydrolyzable silyl group may be subjected to hydrolytic condensation with the vinyl polymer segment (a2) to bond a polysiloxane segment precursor to the silanol group and / or the hydrolyzable silyl group directly bonded to the carbon atom.

[0070] Step 2 is a step of mixing a silane compound containing a silanol group and / or a hydrolyzable silyl group with inorganic particles (m). As the silane compound, a general-purpose silane compound containing a silanol group and / or a hydrolyzable silyl group, which will be described later, can be used. At this time, if there is a group to be introduced into the polysiloxane segment, a silane compound having the group to be introduced is used in combination. For example, when an aryl group is to be introduced, a silane compound having both an aryl group and a silanol group and / or a hydrolyzable silyl group may be used in combination as appropriate. Also, when a group having a polymerizable double bond is to be introduced, a silane compound having both a group having a polymerizable double bond and a silanol group and / or a hydrolyzable silyl group may be used in combination. In order to introduce an epoxy group into the resulting polysiloxane, an epoxy group-containing silane compound having both a silanol group and / or a hydrolyzable silyl group may be used at the same time.

[0071] A known dispersion method can be used for mixing. Examples of mechanical means include a disperser, a disperser having stirring blades such as a turbine blade, a paint shaker, a roll mill, a ball mill, an attritor, a sand mill, a bead mill, etc., and in order to mix uniformly, dispersion by a bead mill using a dispersion medium such as glass beads or zirconia beads is preferred.

[0072] Examples of bead mills include Star Mill manufactured by Ashizawa Finetech Co., Ltd.; MSC-MILL, SC-MILL, and Attritor MA01SC manufactured by Mitsui Mining Co., Ltd.; Nano Grain Mill, Pico Grain Mill, Pure Grain Mill, Mega Capper Grain Mill, Cera Power Grain Mill, Dual Grain Mill, AD Mill, Twin AD Mill, Basket Mill, and Twin Basket Mill manufactured by Asada Iron Works Co., Ltd.; and Apex Mill, Ultra Apex Mill, and Super Apex Mill manufactured by Kotobuki Industries Co., Ltd.

[0073] Step 3 is a step of condensing a silane compound containing a silanol group and / or a hydrolyzable silyl group. In this step 3, the silane compound containing a silanol group and / or a hydrolyzable silyl group is condensed to generate a siloxane bond. When the silanol group and / or the hydrolyzable silyl group of the polysiloxane segment (a1) and the silanol group and / or the hydrolyzable silyl group of the vinyl polymer segment (a2) undergo a dehydration condensation reaction, a bond represented by the general formula (6) is generated. Therefore, in the general formula (6), the carbon atom constitutes a part of the vinyl polymer segment (a2), and the silicon atom bonded only to the oxygen atom constitutes a part of the polysiloxane segment (a1). In addition, by condensing the silane compound containing a silanol group and / or a hydrolyzable silyl group with the inorganic particles (m) in a mixed state, a siloxane bond is formed between the silane compound containing a silanol group and / or a hydrolyzable silyl group and the inorganic particles (m), and the polysiloxane segment (a1) and the inorganic particles (m) are chemically bonded to each other.

[0074] In the composite resin (A), the bonding position between the polysiloxane segment (a1) and the vinyl polymer segment (a2) is arbitrary. Examples of the composite resin (A) include a composite resin having a graft structure in which the polysiloxane segment (a1) is chemically bonded to the vinyl polymer segment (a2) as a side chain, and a composite resin having a block structure in which the vinyl polymer segment (a2) and the polysiloxane segment (a1) are chemically bonded.

[0075] As the silane compound containing a silanol group and / or a hydrolyzable silyl group used in steps 1 to 3, a general-purpose silane compound can be used. Examples of the organotrialkoxysilane include methyltrimethoxysilane, methyltriethoxysilane, methyltri-n-butoxysilane, ethyltrimethoxysilane, n-propyltrimethoxysilane, iso-butyltrimethoxysilane, cyclohexyltrimethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, and other organotrialkoxysilanes; dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldi-n-butoxysilane, diethyldimethoxysilane, methylcyclohexyldimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and other diorganodialkoxysilanes; and chlorosilanes such as methyltrichlorosilane, ethyltrichlorosilane, vinyltrichlorosilane, dimethyldichlorosilane, diethyldichlorosilane, and other chlorosilanes.

[0076] In addition, tetrafunctional alkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, or tetra-n-propoxysilane, or partial hydrolysis condensates of the tetrafunctional alkoxysilane compounds, can be used in combination within a range that does not impair the effects of the present invention. When using a tetrafunctional alkoxysilane compound or a partial hydrolysis condensate thereof in combination, it is preferable to use them in combination so that the silicon atoms of the tetrafunctional alkoxysilane compound do not exceed 20 mol% relative to the total silicon atoms constituting the polysiloxane segment (a1).

[0077] In addition, metal alkoxide compounds of metals other than silicon atoms, such as boron, titanium, zirconium, or aluminum, can be used in combination within a range that does not impair the effects of the present invention. For example, it is preferable to use the above-mentioned metal alkoxide compounds in combination within a range in which the metal atoms contained in the metal alkoxide compounds do not exceed 25 mol% relative to the total silicon atoms constituting the polysiloxane segment (a1).

[0078] In the silane compound containing a silanol group and / or a hydrolyzable silyl group used to form the polysiloxane segment (a1), if the monoalkyltrialkoxysilane having an alkyl group with 1 to 4 carbon atoms is 40 mol % or more, the hydrolysis and condensation of the polysiloxane segment (a1) proceeds easily, and the bond becomes stronger, so that the heat resistance is excellent, which is preferable. In the monoalkyltrialkoxysilane, the alkoxy group preferably has 1 to 4 carbon atoms, and the alkyl group preferably has 1 to 2 carbon atoms.

[0079] Specific examples of monoalkyltrialkoxysilanes having an alkyl group having 1 to 4 carbon atoms include methyltrimethoxysilane, methyltriethoxysilane, methyltri-n-butoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltri-n-butoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, n-butyltrimethoxysilane, and butyltriethoxysilane, and preferably methyltrimethoxysilane.

[0080] In addition, as a silane compound having both a group having a polymerizable double bond and a silanol group and / or a hydrolyzable silyl group used when introducing a group having a polymerizable double bond, for example, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriacetoxysilane, vinyltrichlorosilane, 2-trimethoxysilylethylvinylether, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 3-(meth)acryloyloxypropyltrichlorosilane, etc. are used in combination. Among them, vinyltrimethoxysilane and 3-(meth)acryloyloxypropyltrimethoxysilane are preferred because they can easily proceed with the hydrolysis reaction and can easily remove by-products after the reaction.

[0081] In addition, to introduce an epoxy group into the polysiloxane segment (a1), an epoxy group-containing silane compound may be used. Examples of the epoxy group-containing silane compound include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxyethoxysilane, γ-glycidoxypropyltriacetoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxyethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxyethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxyethoxysilane. Ethyltriacetoxysilane, γ-glycidoxypropyldimethoxymethylsilane, γ-glycidoxypropyldiethoxymethylsilane, γ-glycidoxypropyldimethoxyethoxymethylsilane, γ-glycidoxypropyldiacetoxymethylsilane, β-(3,4-epoxycyclohexyl)ethyldimethoxymethylsilane, β-(3,4-epoxycyclohexyl)ethyldiethoxymethylsilane, β-(3,4-epoxycyclohexyl)ethyldimethoxyethoxymethylsilane, β-(3,4-epoxycyclohexyl)ethyldimethoxyethoxymethylsilane, β-(3,4-epoxycyclohexyl)ethyldiacetoxymethylsilane, γ-glycidoxypropyldimethoxyethylsilane, γ-glycidoxypropyldiethoxyethylsilane, γ-glycidoxypropyldimethoxyethoxyethylsilane, γ-glycidoxypropyldiacetoxyethylsilane, β-(3,4-epoxycyclohexyl)ethyldimethoxyethylsilane, β-(3,4-epoxycyclohexyl)ethyldiethoxyethylsilane, β-(3,4-epoxycyclohexyl)ethyldimethoxyethoxyethylsilane silane, β-(3,4-epoxycyclohexyl)ethyldiacetoxyethylsilane, γ-glycidoxypropyldimethoxyisopropylsilane, γ-glycidoxypropyldiethoxyisopropylsilane, γ-glycidoxypropyldimethoxyethoxyisopropylsilane, γ-glycidoxypropyldiacetoxyisopropylsilane, β-(3,4-epoxycyclohexyl)ethyldiethoxyisopropylsilane, β-(3,4-epoxycyclohexyl)ethyldiethoxyisopropylsilane, β-(3,4-epoxycyclohexyl)ethyldimethoxyethoxyisopropylsilane, β-(3,4-epoxycyclohexyl)ethyldiacetoxyisopropylsilane, γ-glycidoxypropylmethoxydimethylsilane, γ-glycidoxypropylethoxydimethylsilane, γ-glycidoxypropylmethoxyethoxydimethylsilane, γ-glycidoxypropylacetoxydimethylsilane, β-(3,4-epoxycyclohexyl)ethylmethoxydimethylsilane, β-(3,4-epoxycyclohexyl)ethylethoxydimethylsilane, β-( 3,4-epoxycyclohexyl)ethyl methoxyethoxydimethylsilane, β-(3,4-epoxycyclohexyl)ethyl acetoxydimethylsilane, γ-glycidoxypropyl methoxydiethylsilane, γ-glycidoxypropyl ethoxydiethylsilane, γ-glycidoxypropyl methoxyethoxydiethylsilane, γ-glycidoxypropyl acetoxydiethylsilane, β-(3,4-epoxycyclohexyl)ethyl methoxydiethylsilane, β-(3,4-epoxycyclohexyl)ethyl ethoxydiethylsilane, β-(3,4-epoxycyclohexyl)ethyl β-(3,4-epoxycyclohexyl)ethyl methoxyethoxydiethyl silane, β-(3,4-epoxycyclohexyl)ethyl acetoxydiethyl silane, γ-glycidoxypropyl methoxydiisopropyl silane, γ-glycidoxypropyl ethoxydiisopropyl silane, γ-glycidoxypropyl methoxyethoxydiisopropyl silane, γ-glycidoxypropyl acetoxydiisopropyl silane, β-(3,4-epoxycyclohexyl)ethyl methoxydiisopropyl silane, β-(3,4-epoxycyclohexyl)ethyl ethoxydiisopropyl Lusilane, β-(3,4-epoxycyclohexyl)ethyl methoxyethoxydiisopropyl silane, β-(3,4-epoxycyclohexyl)ethyl acetoxydiisopropyl silane, γ-glycidoxypropyl methoxyethoxymethyl silane, γ-glycidoxypropyl acetoxymethoxymethyl silane, γ-glycidoxypropyl acetoxyethoxymethyl silane, β-(3,4-epoxycyclohexyl)ethyl methoxyethoxymethyl silane, β-(3,4-epoxycyclohexyl)ethyl methoxyacetoxymethyl silane, β-(3,4-epoxycyclohexyl)ethylethoxyacetoxymethylsilane, γ-glycidoxypropylmethoxyethoxyethylsilane, γ-glycidoxypropylacetoxymethoxyethylsilane, γ-glycidoxypropylacetoxyethoxyethylsilane, β-(3,4-epoxycyclohexyl)ethylmethoxyethoxyethylsilane, β-(3,4-epoxycyclohexyl)ethylmethoxyacetoxyethylsilane, β-(3,4-epoxycyclohexyl)ethylethoxyacetoxyethylsilane, γ-glycidoxypropylmeth Glycidoxypropyl acetoxymethoxyisopropyl silane, Glycidoxypropyl acetoxyethoxyisopropyl silane, β-(3,4-epoxycyclohexyl)ethyl methoxyethoxyisopropyl silane, β-(3,4-epoxycyclohexyl)ethyl methoxyacetoxyisopropyl silane, β-(3,4-epoxycyclohexyl)ethyl ethoxyacetoxyisopropyl silane, Glycidoxymethyl trimethoxysilane, Glycidoxymethyl triethoxysilane, α-glycidoxypropyl acetoxyethoxyisopropyl silane, α-Glycidoxyethyltrimethoxysilane, α-Glycidoxymethyltrimethoxysilane, β-Glycidoxyethyltrimethoxysilane, β-Glycidoxymethyltrimethoxysilane, α-Glycidoxypropyltrimethoxysilane, α-Glycidoxypropyltriethoxysilane, β-Glycidoxypropyltrimethoxysilane, β-Glycidoxypropyltriethoxysilane, γ-Glycidoxypropyltripropoxysilane, γ-Glycidoxypropyltributoxysilane, γ-Glycidoxypropyltriphenoxysilane, α-Glycidoxy Butyltrimethoxysilane, α-glycidoxybutyltriethoxysilane, β-glycidoxybutyltrimethoxysilane, β-glycidoxybutyltriethoxysilane, γ-glycidoxybutyltrimethoxysilane, γ-glycidoxybutyltriethoxysilane, (3,4-epoxycyclohexyl)methyltrimethoxysilane, (3,4-epoxycyclohexyl)methyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltripoxysilane, β-(3,4-epoxycyclohexyl)ethyltripoxysilane,β-(3,4-epoxycyclohexyl)ethyltriphenoxysilane, γ-(3,4-epoxycyclohexyl)propyltrimethoxysilane, γ-(3,4-epoxycyclohexyl)propyltriethoxysilane, δ-(3,4-epoxycyclohexyl)butyltrimethoxysilane, δ-(3,4-epoxycyclohexyl)butyltriethoxysilane, glycidoxymethylmethyldimethoxysilane, glycidoxymethylmethyldiethoxysilane, α-glycidoxyethylmethyldimethoxysilane, α-glycidoxyethylmethyldiethoxysilane, β-glycidoxyethylmethyldimethoxysilane, β-glycidoxyethylmethyldiethoxysilane, α-glycidoxypropylmethyldimethoxysilane, α-glycidoxypropylmethyldimethoxysilane Examples of the silane include glycidoxypropyl dimethoxysilane, β-glycidoxypropyl methyl diethoxysilane, γ-glycidoxypropyl methyl dimethoxysilane, γ-glycidoxypropyl methyl diethoxysilane, γ-glycidoxypropyl methyl dipropoxysilane, γ-glycidoxypropyl methyl dibutoxysilane, γ-glycidoxypropyl methyl dimethoxyethoxysilane, γ-glycidoxypropyl methyl diphenoxysilane, γ-glycidoxypropyl ethyl dimethoxysilane, γ-glycidoxypropyl ethyl diethoxysilane, γ-glycidoxypropyl ethyl dipropoxysilane, γ-glycidoxypropyl vinyl dimethoxysilane, and γ-glycidoxypropyl vinyl diethoxysilane.

[0082] To introduce the group represented by formula (3) into the polysiloxane segment (a1), a silane compound having the group represented by formula (3) may be used. Specific examples of the silane compound having the group represented by formula (3) include p-styryltrimethoxysilane, p-styryltriethoxysilane, etc.

[0083] In step 2, a part or all of the silane compound containing a silanol group and / or a hydrolyzable silyl group to be mixed with the inorganic particles (m) may be hydrolyzed and condensed. Furthermore, a dispersion medium may be used for the purpose of adjusting the solid content and viscosity. The dispersion medium may be any liquid medium that does not impair the effects of the present invention, and examples of the dispersion medium include various organic solvents, water, liquid organic polymers, and monomers.

[0084] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and methyl isobutyl ketone (MIBK); cyclic ethers such as tetrahydrofuran (THF), and dioxolane; esters such as methyl acetate, ethyl acetate, and butyl acetate; aromatics such as toluene and xylene; and alcohols such as carbitol, cellosolve, methanol, isopropanol, butanol, propylene glycol monomethyl ether, and normal propyl alcohol. These can be used alone or in combination.

[0085] The coating agent used in the present invention may contain, in addition to the composite resin (A), a polymer or monomer having a reactive group that directly contributes to the curing reaction with the composite resin (A).

[0086] When polyisocyanate is used as the reactive compound, it is preferable that the vinyl polymer segment (a2) in the composite resin (A) has an alcoholic hydroxyl group. In this case, it is preferable that the polyisocyanate is contained in an amount of 5 to 50% by weight based on the total amount of the composite resin (A). By containing the polyisocyanate in this range, the conformability of the coating layer when the stretched polyolefin film is deformed is improved. This is presumed to be because the polyisocyanate reacts with the hydroxyl group in the system (which is the hydroxyl group in the vinyl polymer segment (a2) or the hydroxyl group in the active energy ray curable monomer having an alcoholic hydroxyl group described later), forming a urethane bond, which is a soft segment, and acts to relieve the concentration of stress due to curing derived from the polymerizable double bond. There is no particular limitation on the polyisocyanate used, and any known polyisocyanate can be used.

[0087] The isocyanate group in the polyisocyanate is preferably 3 to 30% by weight from the viewpoint of conformality of the coating layer. If the isocyanate group in the polyisocyanate exceeds 30%, the effect of improving conformability due to stress relaxation may not be achieved.

[0088] The reaction between the polyisocyanate and the hydroxyl groups in the system (which are the hydroxyl groups in the vinyl polymer segment (a2) and the hydroxyl groups in the active energy ray-curable monomer having an alcoholic hydroxyl group described below) does not require heating or the like, and the reaction proceeds gradually by leaving the mixture at room temperature. If necessary, the reaction between the alcoholic hydroxyl groups and the isocyanate may be accelerated by heating at 80°C for several minutes to several hours (20 minutes to 4 hours). In this case, a known urethanization catalyst may be used if necessary. The urethanization catalyst is appropriately selected depending on the desired reaction temperature.

[0089] When an active energy ray curable monomer is used as the reactive compound, it is preferable to contain a polyfunctional vinyl monomer having a plurality of vinyl reactive groups. The polyfunctional vinyl monomer is not particularly limited, and known ones such as polyfunctional vinyl monomers and polyfunctional (meth)acrylic monomers can be used. For example, 1,2-ethanediol diacrylate, 1,2-propanediol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, neopentyl glycol diacrylate, tripropylene glycol diacrylate, trimethylolpropane diacrylate, trimethylolpropane triacrylate, tris(2-acryloyloxy)isocyanurate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, di(trimethylolpropane)tetraacrylate, di(pentaerythritol)pentaacrylate, di(pentaerythritol)hexaacrylate, and other polyfunctional (meth)acrylates having two or more polymerizable double bonds in one molecule can be mentioned. In addition, urethane acrylate, polyester acrylate, epoxy acrylate, and the like can also be exemplified as polyfunctional acrylates. These may be used alone or in combination of two or more.

[0090] For example, when the above-mentioned polyisocyanate is used in combination, acrylates having a hydroxyl group, such as pentaerythritol triacrylate and dipentaerythritol pentaacrylate, are preferred. For the purpose of improving abrasion resistance, it is preferable to use a polyvalent (meth)acrylate having an isocyanurate structure. Specific examples include tris(2-acryloyloxyethyl)isocyanurate, ε-caprolactone-modified tris(2-acryloyloxyethyl)isocyanurate, and isocyanuric acid EO-modified diacrylate.

[0091] As the reactive compound, a monofunctional vinyl monomer can be used in combination. For example, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, caprolactone-modified hydroxy (meth)acrylate (e.g., trade name "Placcel" manufactured by Daicel Chemical Industries, Ltd.), mono (meth)acrylate of polyester diol obtained from phthalic acid and propylene glycol, mono (meth)acrylate of polyester diol obtained from succinic acid and propylene glycol, polyethylene glycol mono (meth)acrylate, polypropylene glycol mono (meth)acrylate, pentaerythritol tri (meth)acrylate, 2-hydroxy-3- (meth)acryloyloxypropyl (meth)acrylate, various epoxy esters. Examples of the (meth)acrylic acid esters include hydroxyl group-containing (meth)acrylic acid esters such as (meth)acrylic acid adducts of (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, and other carboxyl group-containing vinyl monomers; vinyl sulfonic acid, styrene sulfonic acid, sulfoethyl (meth)acrylate, and other sulfonic acid group-containing vinyl monomers; acidic phosphate ester vinyl monomers such as 2-(meth)acryloyloxyethyl acid phosphate, 2-(meth)acryloyloxypropyl acid phosphate, 2-(meth)acryloyloxy-3-chloro-propyl acid phosphate, and 2-methacryloyloxyethylphenyl phosphoric acid; and vinyl monomers having a methylol group such as N-methylol (meth)acrylamide. These may be used alone or in combination.

[0092] From the viewpoint of heat resistance of the laminate, when using an active energy ray curable monomer as a reactive compound, it is preferable to use one having a glass transition temperature of -30°C or higher. The upper limit of the glass transition temperature is not particularly limited, but is, for example, 250°C or lower. When two or more active energy ray curable monomers are used in combination, the glass transition temperature of the reactive compound is determined by converting the temperature (K) calculated by the Fox formula below into Celsius temperature (°C). In the formula below, W1, W2, W3, and W4 mean the mass fraction (mass%) of each component. In addition, Tg1, Tg2, Tg3, and Tg4 mean the glass transition temperature (K) of the homopolymer of each component.

[0093]

number

[0094] When an epoxy group is contained, a known curing agent for an epoxy resin can be used as the reactive compound, and examples of such a curing agent include phenol novolac resin, cresol novolac resin, aromatic hydrocarbon formaldehyde resin-modified phenol resin, dicyclopentadiene phenol addition type resin, phenol aralkyl resin (Zylok resin), naphthol aralkyl resin, trimethylolmethane resin, tetraphenylolethane resin, naphthol novolac resin, naphthol-phenol co-condensed novolac resin, naphthol-cresol co-condensed novolac resin, biphenyl-modified phenol resin (a polyhydric phenol compound in which a phenol nucleus is linked by a bismethylene group), biphenyl-modified naphthol resin (a polyhydric naphthol compound in which a phenol nucleus is linked by a bismethylene group), aminotriazine-modified phenol resin (melamine, benzoguanamine, etc.). phenolic compounds such as phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, and the like; amide compounds such as polyamide resins synthesized from dicyandiamide, a dimer of linoleic acid, and ethylenediamine; and amine compounds such as diaminodiphenylmethane, diethylenetriamine, triethylenetetramine, diaminodiphenylsulfone, isophoronediamine, imidazole, BF3-amine complex, and guanidine derivatives.

[0095] It is also preferable to use a polymer or monomer capable of introducing an acidic group into the coating layer as the reactive compound. This is expected to have the effect of making the coating layer easier to peel off from the stretched polyolefin film when subjected to an alkali treatment described later. Examples of such reaction products include acrylic acid, methacrylic acid, maleic acid, itaconic acid, citraconic acid, mesaconic acid, maleic anhydride, 4-methylcyclohex-4-ene-1,2-dicarboxylic anhydride, bicyclo[2.2.2]oct-5-ene-2,3-dicarboxylic anhydride, 1,2,3,4,5,8,9,10-octahydronaphthalene-2,3-dicarboxylic anhydride, 2-octa-1,3-diketospiro[4.4 ]non-7-ene, bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, maleopimaric acid, tetrahydrophthalic anhydride, methyl-bicyclo[2.2.1]hept-5-ene-2,3-dicarboxylic anhydride, methyl-norbornene-5-ene-2,3-dicarboxylic anhydride, norborn-5-ene-2,3-dicarboxylic anhydride, sulfonated styrene, vinylbenzenesulfonamide, and the like.

[0096] It is also preferable to use a polymer or monomer capable of introducing an ether skeleton into the coating layer as the reactive compound, which is expected to have the effect of making the coating layer more easily peelable from the stretched polyolefin film when subjected to an alkali treatment described later.

[0097] The average number of functional groups of the reactive compound can be appropriately adjusted, but is preferably from 2 to 6. The linear expansion coefficient of the coating layer can be designed to be low, and the heat resistance of the laminate can be improved.

[0098] When a reactive compound is used, the amount used is preferably 1 to 85% by weight, more preferably 5 to 80% by weight, of the total solid content of the coating agent containing the composite resin (A). By using the reactive compound within the above range, the adhesion of the coating layer to the stretched polyolefin film and the heat resistance of the laminate can be adjusted.

[0099] In addition to the reactive compound, a curing accelerator can be used as necessary. Various types of curing accelerators can be used, including phosphorus compounds, tertiary amines, imidazoles, organic acid metal salts, Lewis acids, and amine complex salts. In particular, from the viewpoint of excellent curing properties, heat resistance, electrical properties, and moisture resistance reliability, 2-ethyl-4-methylimidazole is preferred as an imidazole compound, triphenylphosphine is preferred as a phosphorus compound, and 1,8-diazabicyclo-[5.4.0]-undecene (DBU) is preferred as a tertiary amine.

[0100] A dispersion medium may be used to adjust the solid content and viscosity of the coating agent used in the present invention. The dispersion medium may be any liquid medium that does not impair the effects of the present invention, and may include various aqueous solvents, organic solvents, liquid organic polymers, etc.

[0101] Examples of organic solvents include ketones such as acetone, methyl ethyl ketone (MEK), and methyl isobutyl ketone (MIBK); cyclic ethers such as tetrahydrofuran (THF), and dioxolane; esters such as methyl acetate, ethyl acetate, and butyl acetate; aromatics such as toluene and xylene; and alcohols such as carbitol, cellosolve, methanol, isopropanol, butanol, propylene glycol monomethyl ether, and normal propyl alcohol. These can be used alone or in combination, but of these, methyl ethyl ketone is preferred from the standpoint of volatility during coating and solvent recovery.

[0102] The liquid organic polymer is a liquid organic polymer that does not directly contribute to the curing reaction, and examples thereof include modified carboxyl group-containing polymers (Floren G-900, NC-500: Kyoeisha), acrylic polymers (Floren WK-20: Kyoeisha), amine salts of special modified phosphate esters (HIPLAAD ED-251: Kusumoto Chemicals), and modified acrylic block copolymers (DISPERBYK2000; BYK-Chemie).

[0103] The coating agent may also contain other additives such as a catalyst, a polymerization initiator, an organic filler, an inorganic filler, an organic solvent, an inorganic pigment, an organic pigment, an extender pigment, a clay mineral, a wax, a surfactant, a stabilizer, a flow adjuster, a dye, a leveling agent, a rheology control agent, an ultraviolet absorber, an antioxidant, and a plasticizer.

[0104] The coating layer is provided by applying the above-mentioned coating agent directly or through a printing layer onto the stretched polyolefin film, followed by drying. It is more preferable to use the reactive functional groups of the composite resin (A) and the inorganic particles (m) to harden them. The hardening method is appropriately selected depending on the reactive functional groups of the composite resin (A) and the inorganic particles (m).

[0105] The method of applying the coating agent is not particularly limited, and any conventionally known method can be used. Examples include various coating methods such as spray coating, direct gravure coating, gravure kiss reverse coating, offset gravure coating, flexo coating, offset coating, bar coating, roll kiss coating, positive rotation roll coating, reverse roll coating, slot die coating, vacuum die coating, (micro)chamber doctor coating, air doctor coating, blade coating, knife coating, spin coating, and dipping coating.

[0106] The thickness of the coating layer can be appropriately adjusted, but is preferably 0.3 μm or more from the viewpoint of heat resistance, and is preferably 6 μm or less from the viewpoint of adhesion.

[0107] The coating agent used in the present invention can be thermally cured, for example, via the silanol group and / or hydrolyzable silyl group of the polysiloxane segment (a1) of the composite resin (A). In the thermal curing, it is possible to heat and cure alone, but it is also possible to use a curing catalyst in combination. Examples of the curing catalyst include inorganic acids such as hydrochloric acid, sulfuric acid, and phosphoric acid; organic acids such as p-toluenesulfonic acid, monoisopropyl phosphate, and acetic acid; inorganic bases such as sodium hydroxide and potassium hydroxide; titanic acid esters such as tetraisopropyl titanate and tetrabutyl titanate; 1,8-diazabicyclo[5.4.0]undecene-7 (DBU), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), 1,4-diazabicyclo[2.2.2]octane (DABCO), tri-n-butylamine, dimethylbenzylamine, monoethanolamine, isopropylamine, butyl ... Examples of the catalyst include various compounds containing a basic nitrogen atom, such as midazole and 1-methylimidazole; various quaternary ammonium salts, such as tetramethylammonium salt, tetrabutylammonium salt, and dilauryldimethylammonium salt, which have a counter anion such as chloride, bromide, carboxylate, or hydroxide; and tin carboxylates, such as dibutyltin diacetate, dibutyltin dioctoate, dibutyltin dilaurate, dibutyltin diacetylacetonate, tin octylate, and tin stearate. The catalyst may be used alone or in combination of two or more.

[0108] When the vinyl polymer segment (a2) contains an alcoholic hydroxyl group and the composition further contains an isocyanate group-containing compound, a urethanization reaction can be caused by adding a catalyst. When the vinyl polymer segment (a2) or the polysiloxane segment (a1) has a group having a polymerizable double bond, the reaction can be carried out by using a thermal polymerization initiator. In addition, when the vinyl polymer segment (a2) or the polysiloxane segment (a1) has an epoxy group, a compound having an epoxy group, a hydroxyl group, a carboxyl group, an acid anhydride, or an amide group can be blended to cause a reaction, and a general-purpose curing agent for epoxy resins can be used.

[0109] It is also possible to use the composite resin (A) in combination with a thermosetting resin. Examples of the thermosetting resin include vinyl resins, unsaturated polyester resins, polyurethane resins, epoxy resins, epoxy ester resins, acrylic resins, phenolic resins, petroleum resins, ketone resins, silicone resins, and modified resins of these resins.

[0110] In the composite resin (A), when the vinyl polymer segment (a2) or the polysiloxane segment (a1) has a polymerizable unsaturated group, it can also be cured by active energy ray curing. More specifically, photocuring is possible by blending a photopolymerization initiator with the coating agent. For photocuring, ultraviolet curing is preferred. As the photopolymerization initiator, a known one may be used, and for example, one or more selected from the group consisting of acetophenones, benzyl ketals, and benzophenones can be preferably used. As the acetophenones, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, etc. As the benzyl ketals, for example, 1-hydroxycyclohexyl-phenyl ketone, benzyl dimethyl ketal, etc. can be used. Examples of the benzophenones include benzophenone, o-benzoyl methyl benzoate, etc. Examples of the benzoins include benzoin, benzoin methyl ether, benzoin isopropyl ether, etc. The photopolymerization initiators may be used alone or in combination of two or more.

[0111] When the composition is cured with ultraviolet light, a polyfunctional (meth)acrylate may be added as necessary to improve the curing density and therefore the heat resistance. A monofunctional (meth)acrylate may also be used.

[0112] The light used for UV curing may be, for example, a low pressure mercury lamp, a high pressure mercury lamp, a metal halide lamp, a xenon lamp, an argon laser, a helium-cadmium laser, or an ultraviolet light emitting diode.

[0113] Alternatively, an electron beam (electron beam) in which electrons are artificially accelerated by an accelerator can be used as the active energy ray, and the coating layer can be formed by electron beam curing. When the coating layer is formed by electron beam curing, the coating agent does not contain a photopolymerization initiator.

[0114] When the coating layer is formed by electron beam curing, it is also preferable to use a polyfunctional or monofunctional (meth)acrylate as a reactive compound in addition to the composite resin (A).

[0115] The energy intensity of the electron beam used in electron beam curing is preferably 30,000 to 300,000 eV, and the exposure dose is preferably 5 to 100 kGy·m / min. (kilogray).

[0116] The coating layer is preferably provided by curing the above-mentioned coating agent by active energy ray curing, and more preferably by curing by electron beam curing. When electron beam curing is used, the coating layer does not contain a photopolymerization initiator, so it can be an odorless or odor-suppressed laminate, and there is no concern that the photopolymerization initiator will migrate to the contents when the laminate of the present invention is used as a food packaging material. In addition, when electron beam curing is used, the heat effect on the irradiated object is small, so there is almost no distortion, wrinkles, deformation, etc. due to heat, and it is possible to process at a line speed of 10 to 400 m / min or more.

[0117] Furthermore, when a coating agent is applied so as to contact the stretched polyolefin film and then cured with an electron beam to form a coating layer, the adhesion between the stretched polyolefin film and the coating layer is improved. Such an effect is more pronounced when the composite resin (A) has a methacryloyl group or when an active energy ray curable monomer having a methacryloyl group is used in combination. Therefore, when a printing layer is provided between the stretched polyolefin film and the coating layer, it is preferable to provide the printing layer partially, rather than entirely, on the stretched polyolefin film so that there is an area where the stretched polyolefin film and the coating layer are in contact with each other.

[0118] (Adhesive layer) The stretched polyolefin film and the heat seal layer can be bonded together by any method, but as an example, they can be bonded together using a two-component curing adhesive containing a polyol composition and a polyisocyanate composition. In this specification, the cured coating film of the two-component curing adhesive is referred to as the adhesive layer.

[0119] The polyol composition includes a polyol having a plurality of hydroxyl groups, such as glycols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, bishydroxyethoxybenzene, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol;

[0120] Trifunctional or tetrafunctional aliphatic alcohols such as glycerin, trimethylolpropane, and pentaerythritol; Bisphenols such as bisphenol A, bisphenol F, hydrogenated bisphenol A, and hydrogenated bisphenol F; Dimer diol; polyether polyols obtained by addition polymerization of alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide, styrene oxide, epichlorohydrin, tetrahydrofuran, and cyclohexylene in the presence of a polymerization initiator such as the glycols or trifunctional or tetrafunctional aliphatic alcohols; a polyether urethane polyol obtained by further polymerizing a polyether polyol with the aromatic or aliphatic polyisocyanate;

[0121] polyester polyols (1), which are reaction products of polyesters obtained by ring-opening polymerization of cyclic ester compounds such as propiolactone, butyrolactone, ε-caprolactone, σ-valerolactone, β-methyl-σ-valerolactone, etc., with polyhydric alcohols such as the above-mentioned glycols, glycerin, trimethylolpropane, pentaerythritol, etc.; Polyester polyol (2) obtained by reacting a difunctional polyol such as the glycol, dimer diol, or bisphenol with a polycarboxylic acid: (3) a polyester polyol obtained by reacting a trifunctional or tetrafunctional aliphatic alcohol with a polycarboxylic acid; (4) a polyester polyol obtained by reacting a difunctional polyol with the above-mentioned trifunctional or tetrafunctional aliphatic alcohol and a polycarboxylic acid; Polyester polyols (5), which are polymers of hydroxyl acids such as dimethylolpropionic acid and castor oil fatty acid;

[0122] polyester polyether polyols obtained by reacting the polyester polyols (1) to (5) and the polyether polyols with an aromatic or aliphatic polyisocyanate; polyester polyurethane polyols obtained by polymerizing the polyester polyols (1) to (5) with aromatic or aliphatic polyisocyanates; Examples of the polyol include castor oil-based polyols such as castor oil, dehydrated castor oil, hydrogenated castor oil which is a hydrogenated product of castor oil, and 5 to 50 moles of alkylene oxide adduct of castor oil, and mixtures thereof.

[0123] Examples of the polyvalent carboxylic acid used in the preparation of the polyester polyols (2) to (4) include aliphatic dicarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, dodecanedicarboxylic acid, maleic anhydride, fumaric acid, 1,3-cyclopentanedicarboxylic acid, and 1,4-cyclohexanedicarboxylic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, orthophthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, and 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid; and anhydrides or ester-forming derivatives of these aliphatic or dicarboxylic acids; p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids, and polybasic acids such as dimer acid.

[0124] The polyol preferably includes at least one of a polyether polyol or a polyester polyol.

[0125] The number average molecular weight of the polyol is not particularly limited, but is preferably, for example, from 300 to 4000. In this specification, the number average molecular weight is a value measured by gel permeation chromatography (GPC) under the following conditions.

[0126] Measuring device: Tosoh Corporation HLC-8320GPC Column: Tosoh Corporation TSKgel 4000HXL, TSKgel 3000HXL, TSKgel 2000HXL, TSKgel 1000HXL Detector: RI (differential refractometer) Data processing: Tosoh Corporation Multistation GPC-8020modelII Measurement conditions: Column temperature 40℃ Solvent Tetrahydrofuran Flow rate 0.35ml / min Standard: Monodisperse polystyrene Sample: 100 μl of tetrahydrofuran solution containing 0.2% by mass of resin solids filtered through a microfilter

[0127] The polyisocyanate composition contains a polyisocyanate compound having a plurality of isocyanate groups. As the polyisocyanate compound, a conventionally known compound can be used without any particular limitation, and examples thereof include aromatic diisocyanates, araliphatic diisocyanates, aliphatic diisocyanates, alicyclic diisocyanates, and biuret compounds, nurate compounds, adduct compounds, allophanate compounds, carbodiimide modified compounds, uretdione modified compounds, and urethane prepolymers obtained by reacting these polyisocyanates with polyols, and these compounds can be used alone or in combination.

[0128] Examples of aromatic diisocyanates include, but are not limited to, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, polymethylene polyphenyl polyisocyanate (also called polymeric MDI or crude MDI), 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0129] The araliphatic diisocyanate means an aliphatic isocyanate having one or more aromatic rings in the molecule, and examples thereof include, but are not limited to, m- or p-xylylene diisocyanate (also known as XDI), α,α,α',α'-tetramethylxylylene diisocyanate (also known as TMXDI), and the like.

[0130] Examples of aliphatic diisocyanates include, but are not limited to, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0131] Examples of alicyclic diisocyanates include, but are not limited to, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate, isophorone diisocyanate (also known as IPDI), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatomethyl)cyclohexane.

[0132] The polyol used in the synthesis of the urethane prepolymer may be the same as those exemplified above, and it is preferable to use at least one of polyalkylene glycol and polyester polyol.

[0133] For flexible packaging substrates, polyisocyanates obtained by reacting aromatic polyisocyanates with polyalkylene glycols having a number average molecular weight in the range of 200 to 6,000, and polyisocyanates obtained by reacting aromatic polyisocyanates with polyester polyols having a number average molecular weight in the range of 200 to 3,000 are preferred because they can impart appropriate flexibility to the cured product. Polyisocyanates with an isocyanate content of 5 to 20% by mass as determined by titration method (using di-n-butylamine) are preferred because they provide appropriate resin viscosity and excellent coatability.

[0134] On the other hand, for hard substrates, polyisocyanates obtained by reacting aromatic polyisocyanates with polyester polyols having a number average molecular weight in the range of 200 to 3,000, and polyisocyanates obtained by reacting aromatic polyisocyanates with a mixture of polyester polyols having a number average molecular weight in the range of 200 to 3,000 and polyalkylene glycols having a number average molecular weight in the range of 200 to 6,000 are preferred from the viewpoint of excellent adhesive strength. Polyisocyanates having an isocyanate content of 5 to 20 mass% according to a standard method (using di-n-butylamine) are also preferred from the viewpoint of appropriate resin viscosity and excellent coatability.

[0135] When the polyisocyanate compound is a urethane prepolymer, the polyisocyanate and polyol used in the synthesis reaction preferably have an equivalent ratio [NCO] / [OH] of isocyanate groups to hydroxyl groups in the range of 1.5 to 5.0, since this brings the viscosity of the adhesive into an appropriate range and provides good coatability.

[0136] The adhesive may contain components other than the above-mentioned components. The other components may be contained in either or both of the polyol composition and the polyisocyanate composition, or may be prepared separately from these and mixed with the polyol composition and the polyisocyanate composition just before application of the adhesive. Each component will be described below.

[0137] The adhesive used in the present invention may contain a catalyst, such as a metal catalyst, an amine catalyst, or an aliphatic cyclic amide compound.

[0138] Examples of the metal catalyst include metal complex catalysts, inorganic metal catalysts, and organic metal catalysts. Examples of the metal complex catalyst include acetylacetonate salts of metals selected from the group consisting of Fe (iron), Mn (manganese), Cu (copper), Zr (zirconium), Th (thorium), Ti (titanium), Al (aluminum), and Co (cobalt), such as iron acetylacetonate, manganese acetylacetonate, copper acetylacetonate, and zirconia acetylacetonate.

[0139] Examples of inorganic metal catalysts include those selected from Sn, Fe, Mn, Cu, Zr, Th, Ti, Al, Co, etc.

[0140] Examples of the organometallic catalyst include organozinc compounds such as zinc octylate, zinc neodecanoate, and zinc naphthenate; organotin compounds such as stannous diacetate, stannous dioctoate, stannous dioleate, stannous dilaurate, dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, and dibutyltin dichloride; organonickel compounds such as nickel octylate and nickel naphthenate; organocobalt compounds such as cobalt octylate and cobalt naphthenate; organobismuth compounds such as bismuth octylate, bismuth neodecanoate, and bismuth naphthenate; titanium compounds such as tetraisopropyloxytitanate, dibutyltitanium dichloride, tetrabutyltitanium, butoxytitanium trichloride, aliphatic diketones, aromatic diketones, and titanium chelate complexes having at least one of alcohols having 2 to 10 carbon atoms as a ligand.

[0141] Examples of the amine catalyst include triethylenediamine, 2-methyltriethylenediamine, quinuclidine, 2-methylquinuclidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N",N"-pentamethyl-(3-aminopropyl)ethylenediamine, N,N,N',N",N"-pentamethyldipropylenetriamine, N,N,N',N'-tetramethylhexamethylenediamine, bis(2-dimethylaminoethyl)ether, dimethylethanolamine, dimethylisopropanolamine, dimethylaminoethoxyethanol, N,N-dimethyl-N'-(2-hydroxyethyl)ethylenediamine, N,N-dimethyl-N'-(2-hydroxyethyl)propanediamine, bis(dimethylaminopropyl)amine, bis(dimethylaminopropyl)isopropanediamine, and the like. lopanolamine, 3-quinuclidinol, N,N,N',N'-tetramethylguanidine, 1,3,5-tris(N,N-dimethylaminopropyl)hexahydro-S-triazine, 1,8-diazabicyclo[5.4.0]undecene-7, N-methyl-N'-(2-dimethylaminoethyl)piperazine, N,N'-dimethylpiperazine, dimethylcyclohexylamine, N-methylmorpholine, N-ethylmorpholine, 1-methylimidazole, 1 ,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, 1-dimethylaminopropylimidazole, N,N-dimethylhexanolamine, N-methyl-N'-(2-hydroxyethyl)piperazine, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)-2-methylimidazole, 1-(2-hydroxypropyl)-2-methylimidazole, and the like.

[0142] Examples of the aliphatic cyclic amide compound include δ-valerolactam, ε-caprolactam, ω-enantholactam, η-capryllactam, β-propiolactam, etc. Among these, ε-caprolactam is more effective in promoting hardening.

[0143] The adhesive used in the present invention may contain an acid anhydride. Examples of the acid anhydride include cyclic aliphatic acid anhydrides, aromatic acid anhydrides, and unsaturated carboxylic acid anhydrides, and one or more of them may be used in combination. More specifically, for example, phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic acid anhydride, dodecenyl succinic anhydride, polyadipic anhydride, polyazelaic anhydride, polysebacic anhydride, poly(ethyl octadecanedioic acid) anhydride, poly(phenyl hexadecanedioic acid) anhydride, tetrahydrophthalic anhydride, methyl tetrahydrophthalic anhydride, methyl hexahydrophthalic anhydride, hexahydrophthalic anhydride, methyl hymic anhydride, trialkyl tetrahydrophthalic anhydride, Examples of the anhydride include methylcyclohexene dicarboxylic anhydride, methylcyclohexene tetracarboxylic anhydride, ethylene glycol bistrimellitate dianhydride, HET anhydride, nadic anhydride, methylnadic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexane-1,2-dicarboxylic anhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride, and 1-methyl-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene succinic dianhydride.

[0144] In addition, the above-mentioned compounds may be modified with glycol as the acid anhydride. Examples of glycols that can be used for modification include alkylene glycols such as ethylene glycol, propylene glycol, and neopentyl glycol; and polyether glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene ether glycol. Furthermore, copolymer polyether glycols of two or more of these glycols and / or polyether glycols may be used.

[0145] The adhesive used in the present invention may contain a coupling agent, such as a silane coupling agent, a titanate coupling agent, or an aluminum coupling agent.

[0146] Examples of the silane coupling agent include aminosilanes such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; epoxysilanes such as β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane; vinylsilanes such as vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; hexamethyldisilazane, γ-mercaptopropyltrimethoxysilane, and the like.

[0147] Examples of titanate coupling agents include tetraisopropoxytitanium, tetra-n-butoxytitanium, butyl titanate dimer, tetrastearyl titanate, titanium acetylacetonate, titanium lactate, tetraoctylene glycol titanate, titanium lactate, and tetrastearoxytitanium.

[0148] An example of the aluminum-based coupling agent is acetoalkoxyaluminum diisopropylate.

[0149] The adhesive used in the present invention may contain a pigment. The pigment is not particularly limited, and examples thereof include organic pigments and inorganic pigments such as extender pigments, white pigments, black pigments, gray pigments, red pigments, brown pigments, green pigments, blue pigments, metal powder pigments, luminescent pigments, and pearlescent pigments described in the Paint Raw Materials Handbook 1970 Edition (edited by the Japan Paint Manufacturers Association), as well as plastic pigments.

[0150] Examples of extender pigments include precipitated barium sulfate, powdered gourd, precipitated calcium carbonate, calcium bicarbonate, kansui stone, alumina white, silica, hydrous fine silica (white carbon), ultrafine anhydrous silica (aerosil), silica sand, talc, precipitated magnesium carbonate, bentonite, clay, kaolin, and yellow earth.

[0151] Specific examples of organic pigments include various insoluble azo pigments such as Benzidine Yellow, Hansa Yellow, Lake 4R, etc.; soluble azo pigments such as Lake C, Carmine 6B, Bordeaux 10, etc.; various (copper) phthalocyanine pigments such as Phthalocyanine Blue, Phthalocyanine Green, etc.; various chlorine dyeing lakes such as Rhodamine Lake, Methyl Violet Lake, etc.; various mordant dye pigments such as Quinoline Lake, Fast Sky Blue, etc.; various vat dye pigments such as Anthraquinone pigments, Thioindigo pigments, Perinone pigments, etc.; various quinacridone pigments such as Synchasia Red B, etc.; various dioxazine pigments such as Dioxazine Violet, etc.; various condensed azo pigments such as Chromophtal, etc.; aniline black, etc.

[0152] Examples of inorganic pigments include various chromates such as yellow lead, zinc chromate, and molybdate orange; various ferrocyanide compounds such as Prussian blue; various metal oxides such as titanium oxide, zinc oxide, mapico yellow, iron oxide, red iron oxide, chrome oxide green, and zirconium oxide; various sulfides or selenides such as cadmium yellow, cadmium red, and mercury sulfide; various sulfates such as barium sulfate and lead sulfate; various silicates such as calcium silicate and ultramarine; various carbonates such as calcium carbonate and magnesium carbonate; various phosphates such as cobalt violet and manganese purple; various metal powder pigments such as aluminum powder, gold powder, silver powder, copper powder, bronze powder, and brass powder; flake pigments of these metals, mica flake pigments; metallic pigments and pearl pigments such as mica flake pigments coated with metal oxides and micaceous iron oxide pigments; graphite, carbon black, and the like.

[0153] Examples of plastic pigments include "Grandol PP-1000" and "PP-2000S" manufactured by DIC Corporation.

[0154] The pigment to be used may be appropriately selected depending on the purpose. For example, it is preferable to use inorganic oxides such as titanium oxide and zinc oxide as white pigments because they have excellent durability, weather resistance, and design properties, and it is preferable to use carbon black as a black pigment.

[0155] The adhesive used in the present invention may contain a plasticizer, such as a phthalic acid plasticizer, a fatty acid plasticizer, an aromatic polycarboxylic acid plasticizer, a phosphoric acid plasticizer, a polyol plasticizer, an epoxy plasticizer, a polyester plasticizer, or a carbonate plasticizer.

[0156] Examples of the phthalic acid plasticizer include phthalic acid ester plasticizers such as dimethyl phthalate, diethyl phthalate, dibutyl phthalate, diisobutyl phthalate, dihexyl phthalate, diheptyl phthalate, di-(2-ethylhexyl) phthalate, di-n-octyl phthalate, dinonyl phthalate, diisononyl phthalate, didecyl phthalate, diisodecyl phthalate, ditridecyl phthalate, diundecyl phthalate, dilauryl phthalate, distearyl phthalate, diphenyl phthalate, dibenzyl phthalate, butyl benzyl phthalate, dicyclohexyl phthalate, octyl decyl phthalate, dimethyl isophthalate, di-(2-ethylhexyl) isophthalate, and diisooctyl isophthalate; and tetrahydrophthalic acid ester plasticizers such as di-(2-ethylhexyl) tetrahydrophthalate, di-n-octyl tetrahydrophthalate, and diisodecyl tetrahydrophthalate.

[0157] Examples of fatty acid plasticizers include adipic acid plasticizers such as di-n-butyl adipate, di-(2-ethylhexyl) adipate, diisodecyl adipate, diisononyl adipate, di(C6-C10 alkyl) adipate, and dibutyl diglycol adipate; azelaic acid plasticizers such as di-n-hexyl azelate, di-(2-ethylhexyl) azelate, and diisooctyl azelate; and di-n-butyl sebacate, di-(2 Sebacic acid plasticizers such as di-n-ethylhexyl) sebacate and diisononyl sebacate; maleic acid plasticizers such as dimethyl maleate, diethyl maleate, di-n-butyl maleate and di-(2-ethylhexyl) maleate; fumaric acid plasticizers such as di-n-butyl fumarate and di-(2-ethylhexyl) fumarate; monomethyl itaconate, monobutyl itaconate, dimethyl itaconate, diethyl itaconate, dibutyl itaconate, Examples of the plasticizer include itaconic acid-based plasticizers such as luitaconate and di-(2-ethylhexyl) itaconate; stearic acid-based plasticizers such as n-butyl stearate, glycerol monostearate, and diethylene glycol distearate; oleic acid-based plasticizers such as butyl oleate, glyceryl monooleate, and diethylene glycol monooleate; citric acid-based plasticizers such as triethyl citrate, tri-n-butyl citrate, acetyl triethyl citrate, acetyl tributyl citrate, and acetyl tri-(2-ethylhexyl) citrate; ricinoleic acid-based plasticizers such as methyl acetyl ricinoleate, butyl acetyl ricinoleate, glyceryl monoricinoleate, and diethylene glycol monoricinoleate; and other fatty acid-based plasticizers such as diethylene glycol monolaurate, diethylene glycol dipelargonate, and pentaerythritol fatty acid esters.

[0158] Examples of aromatic polycarboxylic acid plasticizers include trimellitic acid plasticizers such as tri-n-hexyl trimellitate, tri-(2-ethylhexyl) trimellitate, tri-n-octyl trimellitate, triisooctyl trimellitate, triisononyl trimellitate, tridecyl trimellitate, and triisodecyl trimellitate; and pyromellitic acid plasticizers such as tetra-(2-ethylhexyl) pyromellitate and tetra-n-octyl pyromellitate.

[0159] Examples of the phosphoric acid plasticizer include triethyl phosphate, tributyl phosphate, tri-(2-ethylhexyl) phosphate, tributoxyethyl phosphate, triphenyl phosphate, octyl diphenyl phosphate, cresyl diphenyl phosphate, cresyl phenyl phosphate, tricresyl phosphate, trixylenyl phosphate, tris(chloroethyl) phosphate, tris(chloropropyl) phosphate, tris(dichloropropyl) phosphate, and tris(isopropylphenyl) phosphate.

[0160] Examples of polyol-based plasticizers include glycol-based plasticizers such as diethylene glycol dibenzoate, dipropylene glycol dibenzoate, triethylene glycol dibenzoate, triethylene glycol di-(2-ethylbutyrate), triethylene glycol di-(2-ethylhexoate), and dibutylmethylene bisthioglycolate; and glycerin-based plasticizers such as glycerol monoacetate, glycerol triacetate, and glycerol tributyrate.

[0161] Examples of epoxy plasticizers include epoxidized soybean oil, epoxy butyl stearate, di-2-ethylhexyl epoxy hexahydrophthalate, diisodecyl epoxy hexahydrophthalate, epoxy triglyceride, epoxidized octyl oleate, and epoxidized decyl oleate.

[0162] Examples of polyester plasticizers include adipic acid polyesters, sebacic acid polyesters, and phthalic acid polyesters.

[0163] Examples of carbonate plasticizers include propylene carbonate and ethylene carbonate.

[0164] Other examples of the plasticizer include partially hydrogenated terphenyls, adhesive plasticizers, and polymerizable plasticizers such as diallyl phthalate, acrylic monomers and oligomers, etc. These plasticizers can be used alone or in combination of two or more kinds.

[0165] The adhesive used in the present invention may contain a phosphoric acid compound. Examples of the phosphoric acid compound include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate.

[0166] The adhesive used in the present invention may be in the form of either a solvent-based or solventless type. In this specification, the term "solvent-based" adhesive refers to an adhesive used in a method in which the adhesive is applied to a substrate, heated in an oven or the like to volatilize the organic solvent in the coating film, and then laminated to another substrate, that is, a so-called dry lamination method. Either the polyol composition or the polyisocyanate composition, or both, contain an organic solvent capable of dissolving (diluting) the constituent components of the polyol composition and the polyisocyanate composition.

[0167] Examples of the organic solvent include esters such as ethyl acetate, butyl acetate, cellosolve acetate, etc., ketones such as acetone, methyl ethyl ketone, isobutyl ketone, cyclohexanone, etc., ethers such as tetrahydrofuran, dioxane, etc., aromatic hydrocarbons such as toluene, xylene, etc., halogenated hydrocarbons such as methylene chloride, ethylene chloride, etc., dimethyl sulfoxide, dimethyl sulfamide, etc. The organic solvent used as a reaction medium during the production of the components of the polyol composition and polyisocyanate composition may also be used as a diluent during coating.

[0168] In this specification, the term "solvent-free" adhesive refers to an adhesive form used in a method in which the polyol composition and the polyisocyanate composition do not substantially contain the highly soluble organic solvents, particularly ethyl acetate or methyl ethyl ketone, as exemplified above, and the adhesive is applied to a substrate and then laminated to another substrate without a process of volatilizing the solvent by heating in an oven or the like, that is, a so-called non-solvent lamination method. When the organic solvent used as a reaction medium in the production of the components of the polyol composition and the polyisocyanate composition, or the raw materials thereof, cannot be completely removed, and a trace amount of organic solvent remains in the polyol composition and the polyisocyanate composition, it is understood that the polyol composition does not substantially contain an organic solvent. In addition, when the polyol composition contains a low molecular weight alcohol, the low molecular weight alcohol reacts with the polyisocyanate composition to become part of the coating film, so there is no need to volatilize it after coating. Therefore, such a form is also treated as a solvent-free adhesive, and the low molecular weight alcohol is not considered to be an organic solvent.

[0169] The adhesive is preferably used by blending so that the ratio [NCO] / [OH] of the number of moles of isocyanate groups [NCO] contained in the polyisocyanate composition to the number of moles of hydroxyl groups [OH] contained in the polyol composition is 1.0 to 3.0. This allows for appropriate curing properties to be obtained without depending on the environmental humidity at the time of coating.

[0170] The thickness of the adhesive layer can be adjusted as appropriate, but is, for example, 0.5 μm or more and 6 μm or less.

[0171] (deposited layer) The heat seal layer may further have a vapor deposition layer on the surface on the stretched polyolefin film side. Examples of the vapor deposition layer include vapor deposition layers containing metals such as aluminum, and inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide. From the viewpoints of oxygen barrier property and water vapor barrier property, an aluminum vapor deposition layer is preferred.

[0172] In addition, the stretched polyolefin film may have a vapor-deposited layer containing an inorganic oxide such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, or barium oxide on the surface on the heat seal layer side.

[0173] The deposition layer can be formed by a conventional method, for example, a physical vapor deposition method (PVD method) such as a vacuum deposition method, a sputtering method, or an ion plating method, a chemical vapor deposition method (CVD method) such as a plasma chemical vapor deposition method, a thermal chemical vapor deposition method, or a photochemical vapor deposition method, or the like.

[0174] The thickness of the vapor-deposited film is preferably 1 nm to 100 nm, more preferably 15 nm to 60 nm, and even more preferably 10 nm to 40 nm, in the case of an aluminum vapor-deposited film, and is preferably 1 nm to 140 nm, more preferably 5 nm to 30 nm, and even more preferably 5 nm to 20 nm, in the case of a silicon oxide or aluminum oxide vapor-deposited film.

[0175] Also, for example, a composite film consisting of two or more layers of vapor-deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition. The degree of vacuum in the vapor deposition chamber is 10 -2 ~10 -8After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6 The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The film transport speed is preferably about 10 to 800 m / min, particularly about 50 to 600 m / min.

[0176] (Barrier coat layer) The laminate of the present invention may have a barrier coat layer at any position on the heat seal layer side of the above-mentioned coat layer. In particular, when the laminate of the present invention has a deposition layer, it is preferable to provide the barrier coat layer on the deposition layer. This can prevent cracks from occurring in the deposition layer, and the laminate of the present invention can have excellent gas barrier properties.

[0177] The barrier coat layer can be formed by a known method using a known composition. One example is a film made of a gas barrier composition such as a hydrolyzate of an alkoxide or a hydrolysis condensate of an alkoxide obtained by polycondensing an alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, an acid, water, and an organic solvent. It may further contain a silane coupling agent.

[0178] The alkoxide may be represented by the general formula R 1 n M(OR 2 ) m At least one alkoxide represented by the formula R 1 , R 2 R represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M. As the metal atom M, silicon, zirconium, titanium, aluminum, etc. can be used. 1 , R 2Specific examples of the organic group represented by the formula (1) include alkyl groups such as methyl, ethyl, n-propyl, i-propyl, n-butyl, and i-butyl. These alkyl groups may be the same or different in the same molecule. Specific examples of the alkoxide include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane.

[0179] As the water-soluble polymer, either or both of polyvinyl alcohol resins and ethylene-vinyl alcohol copolymers can be preferably used. These resins may be commercially available. For example, as the ethylene-vinyl alcohol copolymer, EVAL EP-F101 (ethylene content: 32 mol%) manufactured by Kuraray Co., Ltd., and Soarnol D2908 (ethylene content: 29 mol%) manufactured by Nippon Synthetic Chemical Industry Co., Ltd. can be used. As the polyvinyl alcohol, RS-110 (saponification degree = 99%, polymerization degree = 1,000) manufactured by Kuraray Co., Ltd., Kuraray Poval LM-20SO (saponification degree = 40%, polymerization degree = 2,000), and Gohsenol NM-14 (saponification degree = 99%, polymerization degree = 1,400) manufactured by Nippon Synthetic Chemical Industry Co., Ltd. can be used. The content of the water-soluble polymer is, for example, 5 to 500 parts by mass per 100 parts by mass of the alkoxide.

[0180] Tertiary amines are used as the sol-gel catalyst. For example, N,N-dimethylbenzylamine, tripropylamine, tributylamine, tripentylamine, etc. can be used. N,N-dimethylbenzylamine is particularly preferred. For example, 0.01 to 1.0 parts by mass is preferably used per 100 parts by mass of the total amount of the alkoxysilane and the silane coupling agent.

[0181] As the organic solvent, methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, n-butanol, etc. can be used.

[0182] Examples of the silane coupling agent include γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, (3-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, and the like. One or more of them can be used in combination. The amount of the silane coupling agent used is 1 to 20 parts by mass based on 100 parts by mass of the alkoxide.

[0183] The barrier coat layer is formed by applying once or a plurality of times by a conventionally known method such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brush coating, bar coating, or applicator. The thickness of the barrier coat layer is appropriately adjusted, and is, for example, about 0.01 to 100 μm, and more preferably 0.01 to 50 μm.

[0184] (Printing layer) The laminate of the present invention may have a printed layer. The printed layer is a layer on which characters, figures, symbols, other desired patterns, etc. are printed using liquid ink. The printed layer may be provided at any position, but examples include between the stretched polyolefin substrate and the adhesive layer (between a deposition layer or a gas barrier coating layer and the adhesive layer when such a layer is provided), or between the stretched polyolefin substrate and the coating layer. In this specification, liquid ink is a general term for solvent-based inks used in gravure printing or flexographic printing. It may contain resin, colorant, and solvent as essential components, or it may be a so-called clear ink that contains resin and solvent but does not substantially contain colorant.

[0185] The resin used in the liquid ink is not particularly limited, and examples thereof include acrylic resin, polyester resin, styrene resin, styrene-maleic acid resin, maleic acid resin, polyamide resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyvinyl chloride resin, chlorinated polypropylene resin, cellulose-based resin, epoxy resin, alkyd resin, rosin-based resin, rosin-modified maleic acid resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, etc., and one or more of them can be used in combination. Preferably, at least one or two or more selected from polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, and cellulose-based resin are used.

[0186] Colorants used in liquid inks include inorganic pigments such as titanium oxide, red iron oxide, antimony red, cadmium red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite; organic pigments such as soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments; and extender pigments such as calcium carbonate, kaolin clay, barium sulfate, aluminum hydroxide, and talc.

[0187] The organic solvent used in the liquid ink preferably does not contain an aromatic hydrocarbon-based organic solvent. More specifically, examples of the organic solvent include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropanol, and butanol, ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate, aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane, and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane, and these may be used alone or in combination of two or more.

[0188] (Primer layer) The laminate of the present invention may further include a primer layer between the stretched polyolefin film and the coating layer in order to improve the adhesion of the coating layer.

[0189] The heat resistance of the laminate of the present invention can be improved by disposing the above-mentioned coating layer at the position where it comes into contact with a heat seal bar. That is, the thermal shrinkage of the laminate during heat sealing can be suppressed, and heat sealing can be performed at a temperature about 20° C. higher than that of a laminate not having a coating layer.

[0190] Furthermore, the above-mentioned coating layer can be easily peeled off from the stretched polyolefin film by subjecting the laminate of the present invention to an alkali treatment. This method also allows the adhesive layer, printing layer, deposition layer, etc. to be peeled off or dissolved from the substrate (stretched polyolefin or heat seal layer). From this point of view, the laminate of the present invention has excellent recyclability.

[0191] The alkaline solution used to peel off the coating layer is preferably an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, etc. The aqueous sodium hydroxide solution or the aqueous potassium hydroxide solution has a concentration of preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 5% by mass. The pH is preferably 10 or more.

[0192] The alkaline solution may contain a water-soluble organic solvent. Examples of the water-soluble organic solvent include methyl alcohol, ethyl alcohol, propyl alcohol, isopropyl alcohol, ethylene glycol monomethyl ether (methyl cellosolve), ethylene glycol monoethyl ether (cellosolve), ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol dibutyl ether, diethylene glycol monomethyl ether (methyl carbitol), diethylene glycol dimethyl ether, diethylene glycol monoethyl ether (carbitol), diethylene glycol diethyl ether (diethyl carbitol), diethylene glycol monobutyl ether (butyl carbitol), diethylene glycol dibutyl ether, and triethylene glycol. Examples include cholesteryl monomethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, methylene dimethyl ether (methylal), propylene glycol monobutyl ether, tetrahydrofuran, acetone, diacetone alcohol, acetonylacetone, acetylacetone, ethylene glycol monomethyl ether acetate (methyl cellosolve acetate), diethylene glycol monomethyl ether acetate (methyl carbitol acetate), diethylene glycol monoethyl ether acetate (carbitol acetate), ethyl hydroxyisobutyrate, and ethyl lactate, which may be used alone or in combination of two or more.

[0193] The content of the water-soluble organic solvent in the alkaline solution is preferably 0.1% by mass to 20% by mass, and more preferably 1% by mass to 10% by mass.

[0194] The alkaline solution may also contain a non-water-soluble organic solvent. Specific examples of the non-water-soluble organic solvent include alcohol-based solvents such as n-butanol, 2-butanol, isobutanol, and octanol, aliphatic hydrocarbon-based solvents such as hexane, heptane, and normal paraffin, aromatic hydrocarbon-based solvents such as benzene, toluene, xylene, and alkylbenzene, halogenated hydrocarbon-based solvents such as methylene chloride, 1-chlorobutane, 2-chlorobutane, 3-chlorobutane, and carbon tetrachloride, ester-based solvents such as methyl acetate, ethyl acetate, and butyl acetate, ketone-based solvents such as methyl isobutyl ketone, methyl ethyl ketone, and cyclohexanone, and ether-based solvents such as ethyl ether and butyl ether, which may be used alone or in combination of two or more.

[0195] The alkaline solution may contain a surfactant. Examples of the surfactant include various anionic surfactants, nonionic surfactants, cationic surfactants, amphoteric surfactants, etc., and among these, anionic surfactants and nonionic surfactants are preferred.

[0196] Examples of the anionic surfactant include alkylbenzenesulfonates, alkylphenylsulfonates, alkylnaphthalenesulfonates, higher fatty acid salts, sulfate ester salts of higher fatty acid esters, sulfonates of higher fatty acid esters, sulfate ester salts and sulfonates of higher alcohol ethers, higher alkyl sulfosuccinates, polyoxyethylene alkyl ether carboxylates, polyoxyethylene alkyl ether sulfates, alkyl phosphates, polyoxyethylene alkyl ether phosphates, and the like. Specific examples of these include dodecylbenzenesulfonates, isopropylnaphthalenesulfonates, monobutylphenylphenol monosulfonates, monobutylbiphenylsulfonates, and dibutylphenylphenol disulfonates.

[0197] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyglycerin fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkylamines, polyoxyethylene fatty acid amides, fatty acid alkylol amides, alkyl alkanol amides, acetylene glycol, oxyethylene adducts of acetylene glycol, polyethylene glycol polypropylene glycol block copolymers, etc. Polyoxyethylene nonylphenyl ethers, polyoxyethylene octylphenyl ethers, polyoxyethylene dodecylphenyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, fatty acid alkylol amides, acetylene glycol, oxyethylene adducts of acetylene glycol, and polyethylene glycol polypropylene glycol block copolymers are preferred.

[0198] Other surfactants that can be used include silicone surfactants such as polysiloxane oxyethylene adducts; fluorine-based surfactants such as perfluoroalkyl carboxylates, perfluoroalkyl sulfonates, and oxyethylene perfluoroalkyl ethers; and biosurfactants such as spiculisporic acid, rhamnolipids, and lysolecithin.

[0199] These surfactants can be used alone or in combination of two or more. When a surfactant is added, the amount of the surfactant added is preferably in the range of 0.001 to 2 mass %, more preferably 0.001 to 1.5 mass %, and even more preferably 0.01 to 1 mass %, based on the total amount of the alkaline solution.

[0200] The method for peeling off the coating layer from the laminate of the present invention includes a method of immersing the laminate of the present invention in the above-mentioned alkaline solution while heating it to 20 to 90° C. or vibrating it ultrasonically. The heating method is not particularly limited, and known heating methods using heat rays, infrared rays, microwaves, etc. can be used. In addition, the ultrasonic vibration can be, for example, a method of attaching an ultrasonic vibrator to a treatment tank and applying ultrasonic vibration to the alkaline solution.

[0201] The alkaline solution is preferably stirred during the immersion. Examples of the stirring method include a method of mechanically stirring the dispersion of the laminated film contained in the treatment tank with a stirring blade, a method of water flow stirring with a water flow pump, and a method of bubbling with an inert gas such as nitrogen gas. The above-mentioned methods may be used in combination to efficiently peel off the multilayer film.

[0202] The time for immersing the laminate in the alkaline solution varies depending on the structure of the laminate, but is, for example, in the range of 2 minutes to 48 hours.

[0203] <Packaging material> The laminate of the present invention can be used as a multi-layer packaging material for protecting foods, medicines, etc. When used as a multi-layer packaging material, the layer structure can be changed depending on the contents, the environment of use, and the form of use.

[0204] The packaging material of the present invention can be obtained, for example, by overlapping the heat seal layers of the laminate of the present invention so that they face each other, and then heat sealing the peripheral edge. Examples of the bag-making method include folding or overlapping the laminate of the present invention so that the surfaces of the inner layers (the surfaces of the sealant film) face each other, and heat sealing the peripheral edge, for example, by a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope seal type, a grooving seal type, a pleated seal type, a flat bottom seal type, a square bottom seal type, a gusset type, or other heat seal type. The packaging material of the present invention can take various forms depending on the contents, the environment of use, and the form of use. Self-supporting packaging materials (standing pouches) are also possible. Heat sealing can be performed by known methods such as bar seal, rotary roll seal, belt seal, impulse seal, high frequency seal, and ultrasonic seal.

[0205] The packaging material of the present invention is filled with contents through its opening, and the opening is then heat-sealed to produce a product using the packaging material of the present invention. The contents to be filled include confectioneries such as rice crackers, bean snacks, nuts, biscuits and cookies, wafer snacks, marshmallows, pies, semi-dried cakes, candies, and snacks, staple foods such as bread, snack noodles, instant noodles, dried noodles, pasta, aseptically packaged cooked rice, porridge, porridge, packaged rice cakes, and cereal foods, pickles, boiled beans, natto, miso, frozen tofu, tofu, nametake mushrooms, konjac, wild vegetable processed products, jams, peanut cream, salads, frozen vegetables, and processed potato products, livestock processed products such as hams, bacon, sausages, processed chicken products, and corned beef, and fish ham and sausages. Examples of the food products that can be used include processed fishery products such as fish paste, fish paste products, kamaboko, nori, tsukudani, bonito flakes, shiokara, smoked salmon, and spicy cod roe, fruit pulp such as peaches, mandarin oranges, pineapples, apples, pears, and cherries, vegetables such as corn, asparagus, mushrooms, onions, carrots, radishes, and potatoes, prepared foods such as frozen and chilled prepared foods, typified by hamburger steaks, meatballs, seafood fries, gyoza dumplings, and croquettes, dairy products such as butter, margarine, cheese, cream, instant creamy powder, and infant formula, liquid seasonings, retort curry, and pet food. The packaging material of the present invention can also be used as a packaging material for cigarettes, medicines such as disposable hand warmers and infusion packs, cosmetics, and vacuum insulation materials. EXAMPLES

[0206] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited thereto. The blending compositions and other numerical values ​​are based on mass unless otherwise specified.

[0207] Details of the compounds used in the examples and comparative examples are as shown in Tables 1 to 4 below.

[0208] [Table 1]

[0209] [Table 2]

[0210] [Table 3]

[0211] [Table 4]

[0212] <Preparation of composite resin (A)> (Synthesis Example 1) Preparation of polysiloxane segment (a1-1) A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 415 parts of MTMS and 756 parts of MPTS, and the mixture was heated to 60°C while stirring under nitrogen gas aeration. Next, a mixture consisting of 0.1 parts of "A-3" and 121 parts of deionized water was added dropwise over 5 minutes. After the dropwise addition was completed, the temperature in the reaction vessel was raised to 80°C, and the mixture was stirred for 4 hours to carry out a hydrolysis condensation reaction, and a reaction product was obtained.

[0213] Methanol and water contained in the obtained reaction product were removed under reduced pressure of 1 to 30 kilopascals (kPa) at 40 to 60°C to obtain 1000 parts of polysiloxane segment (a1-1) having a number average molecular weight of 1000 and an effective component of 75.0%. The "effective component" is the value obtained by dividing the theoretical yield (parts by weight) when all the methoxy groups of the silane monomer used are hydrolyzed and condensed by the actual yield (parts by weight) after the hydrolysis and condensation reaction, that is, calculated by the formula [theoretical yield (parts by weight) when all the methoxy groups of the silane monomer are hydrolyzed and condensed by / actual yield (parts by weight) after the hydrolysis and condensation reaction].

[0214] (Synthesis Example 2) Preparation of polysiloxane segment (a1-2) A reaction vessel equipped with a stirrer, a thermometer, a dropping funnel, a cooling tube, and a nitrogen gas inlet was charged with 442 parts of MTMS and 760 parts of APTS, and the mixture was heated to 60°C while stirring under nitrogen gas aeration. Next, a mixture consisting of 0.1 parts of "A-3" and 129 parts of deionized water was added dropwise over 5 minutes. After the dropwise addition was completed, the temperature in the reaction vessel was raised to 80°C, and the mixture was stirred for 4 hours to carry out a hydrolysis condensation reaction, and a reaction product was obtained.

[0215] The methanol and water contained in the obtained reaction product were removed under reduced pressure of 1 to 30 kilopascals (kPa) and at 40 to 60°C to obtain 1,000 parts of a polysiloxane segment (a1-2) having a number average molecular weight of 1,000 and an active ingredient content of 75.0%.

[0216] (Synthesis Example 3) Preparation of vinyl polymer segment (a2-1) In a reaction vessel similar to that of Synthesis Example 1, 20.1 parts of PTMS, 24.4 parts of DMDMS, and 107.7 parts of n-butyl acetate were charged, and the temperature was raised to 80° C. while stirring under nitrogen gas aeration. Next, a mixture containing 15 parts of MMA, 45 parts of BMA, 39 parts of EHMA, 1.5 parts of AA, 4.5 parts of MPTS, 45 parts of HEMA, 15 parts of n-butyl acetate, and 15 parts of TBPEH was added dropwise to the reaction vessel over 4 hours at the same temperature while stirring under nitrogen gas aeration. After further stirring at the same temperature for 2 hours, a mixture of 0.05 parts of "A-3" and 12.8 parts of deionized water was added dropwise to the reaction vessel over 5 minutes, and the mixture was stirred at the same temperature for 4 hours to allow the hydrolysis and condensation reaction of PTMS, DMDMS, and MPTS to proceed. The reaction product was analyzed by 1H-NMR, and it was found that the trimethoxysilyl group of the silane monomer in the reaction vessel was almost 100% hydrolyzed. Then, the mixture was stirred at the same temperature for 10 hours to obtain a vinyl polymer segment (a2-1) which was a reaction product with a residual amount of TBPEH of 0.1% or less. The residual amount of TBPEH was measured by iodometric titration.

[0217] (Synthesis Example 4) Preparation of vinyl polymer segment (a2-2) In a reaction vessel similar to that of Synthesis Example 1, 17.6 parts of PTMS, 21.3 parts of DMDMS, and 129 parts of n-butyl acetate were charged, and the temperature was raised to 80° C. while stirring under nitrogen gas aeration. Next, a mixture containing 21 parts of MMA, 63 parts of BMA, 54.6 parts of EHMA, 2.1 parts of AA, 6.3 parts of MPTS, 63 parts of HEMA, 21 parts of n-butyl acetate, and 21 parts of TBPEH was added dropwise to the reaction vessel over 4 hours at the same temperature while stirring under nitrogen gas aeration. After further stirring at the same temperature for 2 hours, a mixture of 0.04 parts of "A-3" and 11.2 parts of deionized water was added dropwise to the reaction vessel over 5 minutes, and the mixture was stirred at the same temperature for 4 hours to allow the hydrolysis and condensation reaction of PTMS, DMDMS, and MPTS to proceed. The reaction product was analyzed by 1H-NMR and found that almost 100% of the trimethoxysilyl groups of the silane monomer in the reaction vessel were hydrolyzed. The mixture was then stirred at the same temperature for 10 hours to obtain a vinyl polymer segment (a2-2) containing 0.1% or less of TBPEH remaining.

[0218] (Synthesis Example 5) Preparation of vinyl polymer segment (a2-3) In a reaction vessel similar to that of Synthesis Example 1, 20.1 parts of PTMS, 24.4 parts of DMDMS, and 107.7 parts of n-butyl acetate were charged, and the temperature was raised to 80° C. while stirring under nitrogen gas aeration. Next, a mixture containing 14.5 parts of MMA, 2 parts of BMA, 105 parts of CHMA, 7.5 parts of AA, 4.5 parts of MPTS, 15 parts of HEMA, 15 parts of n-butyl acetate, and 6 parts of TBPEH was added dropwise to the reaction vessel over 4 hours at the same temperature while stirring under nitrogen gas aeration. After further stirring at the same temperature for 2 hours, a mixture of 0.05 parts of "A-3" and 12.8 parts of deionized water was added dropwise to the reaction vessel over 5 minutes, and the mixture was stirred at the same temperature for 4 hours to allow the hydrolysis and condensation reaction of PTMS, DMDMS, and MPTS to proceed. The reaction product was analyzed by 1H-NMR and found that almost 100% of the trimethoxysilyl groups of the silane monomer in the reaction vessel were hydrolyzed. The mixture was then stirred at the same temperature for 10 hours to obtain a vinyl polymer segment (a2-3) containing 0.1% or less of TBPEH remaining.

[0219] (Synthesis Example 6) Preparation of Composite Resin (A-1) 162.5 parts of polysiloxane (a1-1) obtained in Synthesis Example 1 was added to the total amount of vinyl polymer segment (a2-1) obtained in Synthesis Example 3, and stirred for 5 minutes. Then, 27.5 parts of deionized water was added and stirred at 80° C. for 4 hours to carry out a hydrolysis condensation reaction of the reaction product and polysiloxane. The reaction product obtained was distilled under reduced pressure of 10 to 300 kPa and at 40 to 60° C. for 2 hours to remove the produced methanol and water, and then 150 parts of MEK and 27.3 parts of n-butyl acetate were added to obtain 600 parts of composite resin (A-1) consisting of polysiloxane segment (a1-1) and vinyl polymer segment (a2-1) with a non-volatile content of 50.0%.

[0220] (Synthesis Example 7) Preparation of Composite Resin (A-2) The polysiloxane segment (a1-1) obtained in Synthesis Example 1 (562.5 parts) was added to the total amount of the vinyl polymer segment (a2-1) obtained in Synthesis Example 3, and stirred for 5 minutes. Then, 80 parts of deionized water was added and stirred at 80° C. for 4 hours to carry out a hydrolysis condensation reaction between the reaction product and polysiloxane. The reaction product obtained was distilled for 2 hours under reduced pressure of 10 to 300 kPa and at 40 to 60° C. to remove the produced methanol and water. Then, 128.6 parts of MEK and 5.8 parts of n-butyl acetate were added to obtain 600 parts of composite resin (A-2) consisting of polysiloxane segment (a1-1) and vinyl polymer segment (a2-1) with a non-volatile content of 70.0%.

[0221] (Synthesis Example 8) Preparation of Composite Resin (A-3) 87.3 parts of the polysiloxane segment (a1-1) obtained in Synthesis Example 1 was added to the total amount of the vinyl polymer segment (a2-2) obtained in Synthesis Example 4, and the mixture was stirred for 5 minutes. Then, 80 parts of deionized water was added and the mixture was stirred for 4 hours at 80° C. to carry out a hydrolysis condensation reaction between the reaction product and polysiloxane. The reaction product was distilled for 2 hours under reduced pressure of 10 to 300 kPa and at 40 to 60° C. to remove the produced methanol and water. Then, 150 parts of MEK was added to obtain 600 parts of a composite resin (A-3) consisting of the polysiloxane segment (a1-1) and the vinyl polymer segment (a2-2) with a non-volatile content of 50.0%.

[0222] (Synthesis Example 9) Preparation of Composite Resin (A-4) The polysiloxane segment (a1-2) obtained in Synthesis Example 2 (162.5 parts) was added to the total amount of the vinyl polymer segment (a2-3) obtained in Synthesis Example 5, and stirred for 5 minutes. Then, 27.5 parts of deionized water was added and stirred at 80° C. for 4 hours to carry out a hydrolysis condensation reaction of the reaction product and polysiloxane. The reaction product obtained was distilled under reduced pressure of 10 to 300 kPa and at 40 to 60° C. for 2 hours to remove the produced methanol and water. Then, 150 parts of MEK and 27.3 parts of butyl acetate were added to obtain 600 parts of composite resin (A-4) consisting of polysiloxane segment (a1-2) and vinyl polymer segment (a2-3) with a non-volatile content of 50.0%.

[0223] (Synthesis Example 10) Preparation of vinyl polymer segment (a2-4) Into the same reaction vessel as in Synthesis Example 1, 20.1 parts of PTMS as silane compounds, 24.4 parts of DMDMS, and 107.7 parts of MIBK as a solvent were charged, and the mixture was heated to 95° C. with stirring under nitrogen gas aeration.

[0224] Next, a mixture containing 1.5 parts of AA, 1.5 parts of BA, 30.6 parts of MMA, 29.4 parts of BMA, 75 parts of CHMA, 7.5 parts of HEMA, 4.5 parts of MPTS, 6.8 parts of TBPEH, and 15 parts of MIBK was dropped into the reaction vessel over 4 hours at the same temperature while stirring under nitrogen gas aeration, and then stirred at the same temperature for another 2 hours to obtain a reaction liquid containing a vinyl-based polymer having a number average molecular weight of 5800 and a hydroxyl value (OHv) of 64.7 mgKOH / g. A mixture of 0.06 parts of "A-4" and 12.8 parts of deionized water was dropped into the reaction vessel over 5 minutes, and stirred at the same temperature for 5 hours to allow the hydrolysis and condensation reaction of the silane compound to proceed. The reaction product was 1 Analysis by H-NMR showed that almost 100% of the trimethoxysilyl groups of the silane monomer in the reaction vessel were hydrolyzed. The mixture was then stirred at the same temperature for 10 hours to obtain a vinyl polymer segment (a2-4) with a residual amount of TBPEH of 0.1% or less.

[0225] (Preparation Example 1) Preparation of Dispersion of Inorganic Particles (m-1) 651.5 parts of MTMS, 1188.2 parts of MPTS, 1450.4 parts of Aerosil 200, 0.8 parts of "A-4", 258.7 parts of deionized water, and 1450.4 parts of MIBK were mixed and dispersed using Ultra Apex Mill UAM015 manufactured by Kotobuki Industries Co., Ltd. In preparing the dispersion, 70% of the volume of the mill was filled with 100 μm zirconia beads as media in the mill, and the mixture was circulated and ground at a peripheral speed of 10 m / s and a flow rate of 1.5 liters per minute. The circulation grinding was carried out for 30 minutes to obtain a dispersion of inorganic particles (m-1) in which silica particles were dispersed in the mixture.

[0226] (Preparation Example 2) Preparation of Dispersion of Inorganic Particles (m-2) A dispersion of inorganic particles (m-2) was obtained in the same manner as in Preparation Example 1, except that 276.8 parts of MTMS, 504.8 parts of MPTS, 4107.9 parts of IPA-ST, 0.7 parts of "A-4", and 109.9 parts of deionized water were used, and MIBK was not used.

[0227] (Synthesis Example 11) Preparation of Composite Resin (A-5) To 336.8 parts of vinyl polymer segment (a2-4), 886.3 parts of inorganic particle (m-1) dispersion was added, and the mixture was stirred for 5 minutes. Then, 14.7 parts of deionized water was added, and the mixture was stirred at 80 ° C for 4 hours to carry out a hydrolysis condensation reaction between the vinyl polymer segment and the silane compound. The reaction product obtained was distilled under reduced pressure of 1 to 30 kPa at 40 to 60 ° C for 2 hours to remove the produced methanol and water, and then 145.1 parts of MIBK and 417.9 parts of DAA were added to obtain a composite resin (A-5) (solid content 35.0%) with a silica content of 33 wt% and inorganic particles (m-1) bonded thereto.

[0228] (Synthesis Example 12) Preparation of Composite Resin (A-6) A composite resin (A-6) (solid content 45.2%) having a silica content of 50 wt% and bound to inorganic particles (m-2) was obtained in the same manner as in Synthesis Example 11, except that 1217.2 parts of a dispersion of inorganic particles (m-2) was used instead of the dispersion of inorganic particles (m-1), 610.6 parts of MIBK, and no DAA were used.

[0229] <Preparation of Coating Agent> Example 1 The coating agent of Example 1 was prepared by adding 50 parts of TMP3EOTA to 100 parts of the composite resin (A-1) (50 parts in terms of solid content).

[0230] (Example 2) to (Example 4) Coating agents of Examples 2 to 4 were prepared in the same manner as in Example 1, except that the composite resin (A), reactive compound, and their blending amounts were changed to those shown in Table 5.

[0231] Example 5 A mixture of 50 parts of composite resin (A-1) (25 parts in terms of solid content), 25 parts of silica particles (Aerosil 50 manufactured by Nippon Aerosil Co., Ltd., average primary particle diameter about 30 nm) and 175 parts of MIBK was used with Ultra Apex Mill UAM015 manufactured by Kotobuki Industries Co., Ltd., and 30 μm diameter zirconia beads were filled in the mill as media at 50% of the mill volume, and circulation grinding was performed for 30 minutes at a flow rate of 1.5 liters per minute. MIBK was removed using an evaporator, and 100 parts of a dispersion liquid of composite resin (A-1) and silica with a non-volatile content concentration of 50% was obtained. 100 parts of TMP3EOTA was added to this to prepare the coating agent of Example 5.

[0232] (Example 6) to (Example 11) Coating agents of Examples 6 to 11 were prepared in the same manner as in Example 5, except that the composite resin (A), silica particles, reactive compound, and their blending amounts were changed to those shown in Tables 5 and 6.

[0233] Example 12 The coating agent of Example 12 was prepared by adding 35 parts of TMP3EOTA to 100 parts of the composite resin (A-5) (35 parts in terms of solid content).

[0234] (Example 13) to (Example 17) Coating agents of Examples 13 to 17 were obtained in the same manner as in Example 12, except that the composite resin (A), reactive compound, and their blending amounts were changed to those shown in Tables 6 and 7.

[0235] Comparative Example 2 TMP3EOTA was used as the coating agent in Comparative Example 2. Comparative Example 3 A mixture of 50 parts of TMP3EOTA and 50 parts of TCDDA was used as the coating agent in Comparative Example 3. Comparative Example 4 A mixture of 50 parts of TMP3EOTA and 125 parts of MEK-ST-40 was used as the coating agent in Comparative Example 4.

[0236] <Manufacture of Laminate> The prepared coating agent was applied at 2 g / m2 onto a 25 μm-thick stretched polyethylene film (Hibron P, manufactured by Tokyo Ink Co., Ltd.). 2 After the solvent was evaporated, an electron beam was irradiated using an EB device with an energy intensity of 125,000 eV and an exposure dose of 50 kGy m / min (kilogray) to form a coating layer.

[0237] <Evaluation> (Adhesion to substrate) A cellophane tape (TF-12, manufactured by Nichiban Co., Ltd.) was applied to the coating layer, and the degree of peeling when the tape was peeled off in one go was visually judged and rated on a 3-point scale. Note that in Comparative Example 1, no coating layer was formed, so adhesion was not evaluated. 〇: No peeling △: Partly peeled off ×: All peeled off

[0238] (Heat resistance) The laminate was subjected to a thermal gradient heat seal tester (manufactured by Tester Sangyo Co., Ltd.) at a sealing temperature of 140°C to 150°C and a pressure of 3 kg / cm. 2 A heat seal bar was placed in direct contact with the coating layer for 1 second. The condition of the film after the heat seal bar was placed in contact was visually evaluated on a three-level scale. 〇: No wrinkles around the seal △: Slight wrinkles can be seen around the seal area. ×: Wrinkles are clearly visible around the entire seal area.

[0239] (Recyclability) The laminate cut into a size of 2 cm x 2 cm was placed in a 1.5% NaOH aqueous solution and stirred for 1 hour at 85° C. The laminate was then washed and dried, and the presence or absence of peeling of the coating layer was visually checked and rated on a 4-point scale. ◎: All peeled off 〇: Almost completely peeled off △: Partly peeled off ×: No peeling

[0240] [Table 5]

[0241] [Table 6]

[0242] [Table 7]

[0243] As is clear from the Examples and Comparative Examples, the laminate of the present invention exhibited excellent adhesion, heat resistance and recyclability.

Claims

1. A method for producing a laminate including a heat seal layer, a stretched polyolefin film, and a coating layer in this order, comprising: The method for producing a laminate includes applying a composition containing a composite resin (A) having a polysiloxane segment (a1) and a vinyl polymer segment (a2) and an active energy ray-curable monomer, and curing the composition by irradiating with active energy rays to form the coating layer.

2. The method for producing a laminate according to claim 1 , wherein the coating layer further contains inorganic particles (m).

3. The method for producing a laminate according to claim 2 , wherein the composite resin (A) and the inorganic particles (m) are bonded to each other via a siloxane bond in the polysiloxane segment (a1).

4. The method for producing a laminate according to claim 1 , wherein the active energy ray-curable monomer contains a polyfunctional vinyl monomer having a plurality of vinyl reactive groups.

5. 2. The method for producing a laminate according to claim 1, wherein the glass transition temperature of the active energy ray-curable monomer is from -30°C to 250°C.

6. 2. The method for producing a laminate according to claim 1, wherein the content of the active energy ray-curable monomer in the solid content of the composition is 1 to 85 mass %.

7. The method for producing a laminate according to claim 1 , wherein the active energy rays are electron beams.

8. The method for producing a laminate according to claim 1 , further comprising a primer layer disposed between the stretched polyolefin film and the coating layer and in contact with the coating layer.

9. The method for producing a laminate according to claim 1 , further comprising a printing layer disposed between the stretched polyolefin film and the coating layer.

10. The method for producing a laminate according to claim 1 , further comprising: an adhesive layer disposed between the stretched polyolefin film and the heat seal layer; and a printing layer disposed between the stretched polyolefin film and the adhesive layer.

11. A method for producing a packaging material, comprising producing a bag from the laminate obtained by the method for producing a laminate according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Ultrasonic diagnostic apparatus

    JP1983022048A

  • Packaging material for lithium ion battery and manufacturing method thereof

    JP2002216715A

  • Low-elution packaging material

    JP2004238050A

  • Curable aqueous composition

    JP2010090274A

  • Aqueous curable coating composition, and method for producing the same

    JP2012031382A